Simulation of equivalent scale-up design of molten salt electrolyzer with stirrer using dimensional analysis and numerical method - Meng Zhang; Lunxiu Cao; Yuannuo Wang; Hemu Zhao; Yi Li; Wenlong Huang; Hongguo Hou; Chunyuan Zhan; Tingting Liu; Jingyang Wang; Rushan Lin; Yu Zhou; et al. (Annals of Nuclear Energy, 2026)

Restoration of membrane potential rescues organelle function via NS309-mediated KCa activation in aged porcine oocytes - Ying-Yan Jin; Cheng-Lin Zhan; Song-Hee Lee; Ji-Yeon Lee; Xiang-Shun Cui (Theriogenology, 2026)

A cascade reaction pathway enabled by sub-micron bismuth-decorated cathode for aqueous Zn-I2 batteries - Zhuoran Ao; Huixin Ren; Yuxi Guo; Lijing Yan; Zhan Lin (Chemical Engineering Journal, 2026)

Four Decades of Straw and Manure Application Differentially Alter DOM Composition and Transport Risk in a Vertisol - Xin Yang; Yanfeng Zhang; Min Xia; Peixuan Wang; Zhibin Guo; Lin Jin; Linchuan Zhan; Daozhong Wang; Keke Hua (Water, Air, & Soil Pollution, 2026)

Fold-crease induced paper wicking enhancement enabling rapid and high-yield plasma separation - Xianchang Wu; Tonghuan Zhan; Fuzhou Niu; Yange Huang; Heng Wang; Lin Hu; Bing Xu (Analytica Chimica Acta, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Holocene monsoon-driven hydroclimate and wildfire suppression in a northeastern Taiwan montane cloud forest - Shi-Ting Zhan; Pang-Chuan Liu; Abdur Rahman; Ludvig Löwemark; Tsai-Wen Lin; Cheng-Tao Lin; Liang-Chi Wang (Global and Planetary Change, 2026)

Regional heterogeneity and vertical stratification of carbon dynamics in Chinese peatlands - Hui Zhang; Minna Väliranta; Angela Gallego-Sala; Zhan-Yi Lin; Chen-Yu Wang; Yan Zhao; Zheng-Tang Guo (Global and Planetary Change, 2026)

A-site magnesium regulation for defect-optimized perovskite oxides toward efficient and durable alkaline oxygen evolution - Xintong Lv; Kaitao Li; Chengjun Xie; Zijun Xu; Feifei Dong; Yufei Ma; Zhan Lin (Fuel, 2026)

Characterization of soybean proteins with various 7S/11S globulin ratios plus machine learning analysis for associating their corresponding physical and chemical functionalities - Yilai Wan; Xinyu Guo; Zhen Liu; Yanhong Lin; Guandi Chen; Yong Zhan; Shengwei Hu; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2026)

Ultrasensitive and rapid detection of botulinum neurotoxin serotype A via Argonaute-mediated signal cascade with a pregnancy test strip readout - Weiling Yu; Yukang Chen; Shujie Zhang; Ruina Zheng; Zhanyin Lin; Yujun Mei; Qiancheng Zhan; Bowen Xue; Jinxuan Fan; Bo Liu; Song Gao; Yuan-Di Zhao; et al. (Food Chemistry, 2026)

TiO2-facet-dependent effect on CH3SH synthesis from CO2/H2S over KMoS2/TiO2 catalysts - Bang Li; Kaiwen Lu; Xiaohai Zheng; Wei Lin; Qiuqiao Jiang; Ganchang Lei; Shiping Wang; Lijuan Shen; Shijing Liang; Yingying Zhan; Lilong Jiang (Chemical Engineering Journal, 2026)

Corrigendum to “Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration” [Carbohydrate Polymers 352 (2025) 123192] - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2026)

Wine polyphenols in the prevention of metabolic syndrome: a critical review of multitarget mechanisms and translational perspectives - Xiping Kang; Huimin Xue; Kexin Hong; Yuchen Lin; Yunxiao Gao; Weidong Huang; Jicheng Zhan; Yilin You (Critical Reviews in Food Science and Nutrition, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Electronic configuration regulation and photocatalytic nitrogen fixation performance of the fourth-period d7/d8 metal catalysts - Xiaolu Xu; Jingyi Qu; Yangben Chen; Jiahui Lin; Yibo Zhang; Zhan Hu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

Occurrence, variation and risks of viruses in aerosols during rural wastewater collection, treatment and discharge - Yingming Zhu; Su Xu; Yu Zhou; Ruiqi Quan; Jun Zhan; Xuesong Guo; Lin Li; Junxin Liu (Journal of Cleaner Production, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

A fountain pen strategy for writing flexible electronics with low-temperature chemical reactive silver ink - Jiayang Lin; Yi Zhao; Jie You; Fangzu Yang; Ren Hu; Jian-Jia Su; Yuanfei Wu; Lianhuan Han; Dongping Zhan (Chemical Engineering Journal, 2026)

Electro-driven aerobic biological nitrogen fixation for protein and ammonium production by Azotobacter vinelandii with sucrose as the sole carbon source - Liying Ren; Min Zhu; Chen Qi; Guohua Zou; Xinyue Wang; Wei Lu; Min Lin; Zhengfu Zhou; Yuhua Zhan; Yongliang Yan (Bioresource Technology, 2026)

In-situ characterisation of coupled hygrothermal-mechanical responses in roof assemblies: A monitoring study in hot-humid climates - Qiaosheng Zhan; Jinsui Zhou; Xiang Zhou; Shi Yin; Shan Huang; Hankun Lin (Building and Environment, 2026)

Effect of soil organic phosphorus transformations on phosphorus availability during soil drying-wetting events: Insights into abiotic and biotic processes - Jinzhen Zhan; Liwen Lin; Yue Qiu; Sibei Chen; Wei Ji; Yutao Peng; Junhui Yin; Junjie Guo; Guorong Xin; Owen Fenton; Hao Chen (Soil and Tillage Research, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Electron-deficient boron-doped bimetallic (ZnFe) catalyst for high-efficiency photocatalytic nitrogen fixation - Xiaolu Xu; Jiahui Lin; Yangben Chen; Yibo Zhang; Zhan Hu; Jingyi Qu; Zhexiao Zhu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

Performance enhancement in proton exchange membrane water electrolyzers through the metal foam flow fields with orderly arranged pore structure - Li Zhan; Shihao Lin; Qihao Deng; Wenshang Chen; Yi Yu; Guangfu Li; Ben Chen (Fuel, 2026)

Acid-resistant ferrihydrite-spent grain composites for enhanced as and Sb removal from acid mine drainage - Zhongqiang Hu; Zhan Yao; Lin Yu; Jianping Guo; Zhihui Yang; Weichun Yang; Qi Liao; Xi Chen; Shuyan Mi (Environmental Research, 2026)

Storm sequences reduce the wave attenuation capacity of salt marshes - Yuxi Ma; Wenzhen Zhao; Liming Xue; Bas Hofland; Lin Su; Lv Gong; Shiwei Lin; Zhan Hu; Xiuzhen Li; Tjeerd J. Bouma (Estuarine, Coastal and Shelf Science, 2026)

Experimental analysis of warm-season thermal performance of opaque ventilated roofs in cold zone of China - Zhenghao Lin; Jianning Tian; Lin Zhuang; Ying Su; Qiaosheng Zhan (Energy and Buildings, 2026)

Large-Scale Plasma Proteomics Profiles for Predicting Atrial Fibrillation Associated Stroke Risk - Shengkang Huang; Xin Feng; Huilin Wu; Rongxuan Liang; Yuan Gao; Zhaojun Wang; Botao Tang; Jiatong Wu; Junkai Fang; Ziang Yang; Xieraili Tiemuerniyazi; Jiancheng Lin; et al. (Translational Stroke Research, 2026)

Engineering a root-associated bacterium Pseudomonas stutzeri A1501 with nitrogen fixation and phosphate solubilization activities for enhanced growth of host rice - Changyan Yin; Dongqi Wang; Bodan Su; Yaoyao Liu; Yuhua Zhan; Wei Lu; Haichao Feng; Yongliang Yan; Xiubin Ke; Min Lin (Plant and Soil, 2026)

Sexually dimorphic expression and hormonal responsiveness of steroidogenic Cyp genes during gonadal differentiation in mandarin fish - Jieming Zhang; Shengyue Lin; Ziyan Deng; Weijian Chen; Guojun Cai; Min Zhang; Lilin Zhan; Chong Han; Jian Gong; Qiang Li (Fish Physiology and Biochemistry, 2026)

Substrate type and structural complexity drive macrobenthic diversity of coral reefs in the South China Sea - Peng-Jin Zhu; Li-Sha Hu; Zhan-Wei Zhao; Hong-Qiang Yang; Min Hui; Ze-Lin Chen; Yun-Wei Dong (Coral Reefs, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Bone marrow mesenchymal stem cell-derived exosomes exert therapeutic effects on inflammatory bowel disease through miR-148a-3p/Ets-1-dependent inhibition of pyroptosis - Feilong Zhang; Ji Song; Yunjiao Zhang; Hejun Hu; Ping Zhou; Caixiao Xu; Meinan Zhan; Anna Hou; Xiangli Lin; Wenjuan Shen (Human Cell, 2026)

Geological events and climate oscillations shaped the divergence and evolutionary history of Rehmannia species (Orobanchaceae) - Miaozhen Ren; Lin Zhao; Jiangtao Wang; Huiyue Du; Miaomiao Zhao; Xingxue Yang; Shining Huang; Jianfang Li; Zhan-Lin Liu (Molecular Phylogenetics and Evolution, 2026)

Multimodal detection of microplastics in human kidney stones and multi-omics exploration of renal cell metaflammation - Qingli Zeng; Jinhui Tang; Leilei Zhan; Ruiyin Liang; Chuanli Yang; Ruibin Cai; Jieyu Luo; Jia Xu; Tao Liu; Hongyan Wei; Lin Che (Journal of Hazardous Materials, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

A Large-Scale Micro-friction True Triaxial Apparatus for Analyzing the Failure Features of Coarse-Grained Soils Under Complex Stress Conditions - Jia-Jun Pan; Wei Zhao; Zhan-Lin Cheng; Yong-Zhen Zuo (Rock Mechanics and Rock Engineering, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Efficacy and mechanism of a three-dimensional electro-Fenton system combining with Fe-N-C catalyst for Microcystis aeruginosa inactivation - Ze Zhang; Yinhan Lin; Chao Xu; Jiehao Zhan; Beini Gong; Lihua Cui; Qiaoling Xu; Zhujian Huang (Journal of Environmental Chemical Engineering, 2026)

Probiotic supplementation alleviates diet-induced obesity via improving gut immune homeostasis and enhancing immunoglobulin A secretion - Kexin Hong; Huimin Xue; Xiping Kang; Yuchen Lin; Yunxiao Gao; Yunyu Tang; Xiangjun Liu; Jia Liu; Weidong Huang; Jicheng Zhan; Yilin You (Food Research International, 2026)

Synergistic engineering of zincophilic sites and hierarchical porosity in lignin-derived carbon nanofiber networks for ultra-high energy density flexible zinc-ion hybrid capacitors - Lin-Xuan Wu; Bo Wang; Jia-Long Wen; Zhan-hui Yuan; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Shenrong Guben Huanshao Pill enhanced stress resistance and extended the lifespan of Caenorhabditis elegans by activating the oxidative stress system via the DAF-16/FOXO signaling pathway - Yi-Nan Yang; Xin Wang; Hong-Fen Jiang; Jie Yang; Subiy Akbara; Xiao-Qin Yang; Hai-Qing Fan; Guo-Lin Chai; Dong-Qing Fei; Fang-Di Hu; Shuang-Xi Qian; Zhan-Xin Zhang (Biogerontology, 2026)

Identification of Closantel as a small-molecule inhibitor of the compact CRISPR-Cas RNA editor Cas13bt3 - Xulong Chen; Binbin Zhan; Ruyi Shi; Jingxuan Chen; Zhonghui Lin; Zuoan Li (Molecular Diversity, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Design and Motion Performance of an Underwater Two-Stage Towed System with Active Heave Compensation - Zhan Wang; Pengfei Xu; Lei Yang; Meijie Cao; Hailong Lin (Journal of Marine Science and Engineering, 2026)
Underwater towed survey systems are widely used for marine observation, resource exploration, and target identification. While high-speed towing is increasingly required to improve operational efficiency, conventional single-stage towed systems face a critical trade-off: active heave compensation systems are complex and costly, whereas purely passive configurations lack sufficient disturbance rejection at higher speeds. To address this gap, this study proposes a two-stage towing system consisting of a vessel, heavy cable, depressor, light cable, and detection towed body, where the depressor functions as a mechanical low-pass filter. The depressor reduces vessel-induced heave motion transmission by approximately 79% compared with a conventional single-stage system. CFD simulations are conducted to evaluate hydrodynamic performance and extract key coefficients. A lumped-mass dynamic model is established for time-domain motion simulations. An integral sliding-mode controller with vessel heave feedforward compensation is designed to enhance depth-tracking capability. The active controller eliminates step response overshoot and provides robust depth regulation under wave disturbances. Sea trials under real ocean conditions validate the system’s motion stability, demonstrating satisfactory depth-keeping performance at high towing speeds. The simulation results show good agreement with experimental data, confirming the effectiveness of the proposed system and dynamic model. This work offers a practically validated towing platform solution for high-precision underwater survey operations.

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

Hierarchical NiSx@Zn0.1Cd0.9S heterostructures with enhanced charge separation for efficient solar-to-hydrogen conversion - Along Gao; Zihui Yan; Xiaoming Liu; Qi Yuan; Sisi Zhan; Yanqing Li; Jun Lin (Fuel, 2026)

Development of Two Multienzyme Isothermal Rapid Amplification Techniques for the Rapid Visual Detection of Micropterus salmoides rhabdovirus - Qingyue Xu; Yiping Lin; Yixia Ma; Zhantian Liao; Tao Li; Shuai Wang; Chunguo Liu; Zhan Luo; Qingqing Song; Shun Zhou; Yunji Xiu (Journal of Fish Diseases, 2026)
Largemouth bass ( Micropterus salmoides ) is an important freshwater‐cultured species in China. M. salmoides rhabdovirus (MSRV) is a devastating pathogen that causes high mortality (exceeding 90% in acute outbreaks) in largemouth bass fry, posing a severe threat to the global largemouth bass aquaculture industry. To address the urgent demand for rapid, on‐site MSRV detection, two multienzyme isothermal rapid amplification (MIRA)‐derived methods—multienzyme isothermal rapid amplification with fluorescence detection (MIRA‐FLU) and multienzyme isothermal rapid amplification with lateral flow dipstick (MIRA‐LFD)—were established and optimized targeting the conserved nucleoprotein (N) gene of MSRV. The performance of both methods was systematically evaluated, and their practical applicability was verified using clinical samples collected from diseased fish farms. The results demonstrated that both methods exhibited high sensitivity, with a detection limit of 9 copies/μL for the standard plasmid. Both detection methods demonstrated high specificity and showed no cross‐reactivity with other common aquatic viruses, indicating their high specificity for MSRV detection. MIRA‐FLU completed amplification within 25 min at 42°C, while MIRA‐LFD achieved amplification within 12 min at 37°C. MIRA‐FLU is used for real‐time fluorescent quantitative detection, whereas MIRA‐LFD enables visual, instrument‐free reading via lateral flow test strips. In comparative analyses of clinical samples, the diagnostic results of MIRA‐FLU and MIRA‐LFD were compared with those of the standard conventional PCR test and showed nearly 100% consistency. Therefore, our MIRA‐FLU and MIRA‐LFD detection methods demonstrate excellent specificity and sensitivity, providing two simple, rapid and reliable approaches for large‐scale field surveys of MSRV in resource‐limited settings.

Degradation of sulfamethoxazole by a Pseudomonas consortium: co-substrate promotion mechanisms, accelerated immobilization and microbial community dynamics in wastewater application - Yize Liu; Chuanzhou Liang; Ruizhuo Lu; Zhe Liu; Xiongbo Zhan; Zhongxiong Zhou; Lin Liu; Minhua He; Bolin Li; Zhiyu Wei (Journal of Water Process Engineering, 2026)

Crude oil biodegradation by synthetic microbial consortia: Performance and mechanisms under a top-down enrichment strategy - Wenya Wang; Qing Xiao; Ruiqi Lin; Hao Zhou; Yuanyuan Qu; Jingjing Zhan; Xuwang Zhang (Journal of Environmental Chemical Engineering, 2026)

Seismic performance of trussed concrete-filled steel tubular (CFST) hybrid structures: Experiments - Zhan-Shuo Liang; Lin-Hai Han; Ming Xiao (Engineering Structures, 2026)

Effect of Placement Position On the Control of Phosphorus Release From Sediment By Lanthanum-modified Bentonite - Ruixiang Xiong; Jianwei Lin; Yanhui Zhan; Ying Chen (Water, Air, & Soil Pollution, 2026)

Roof-integrated phase change materials for urban heat island mitigation: advances and strategies - H. Zhan; G. Lin (International Journal of Environmental Science and Technology, 2026)

Microbial community robustness and function are associated with yield and multifunctionality under rice rotation in the subtropical Anning River Valley - Junbo Zhou; Qinghua Liu; Ruyi Luo; Juan Zhan; Lin Luo; Xianjun Jiang; Xueyong Pang (Agriculture, Ecosystems & Environment, 2026)

Atmospheric Deposition of Multi-Class Substances into the Ocean: Synthesis of Fluxes, Seasonal Spatial Patterns and Ecological Risks - Qinghao Lin; Xianliang Yi; Junyi Wang; Yiwen Zhang; Jingjing Zhan (Journal of Marine Science and Engineering, 2026)
Atmospheric deposition is increasingly recognized as a significant pathway transporting diverse substances from land to the ocean. However, significant uncertainties persist regarding the magnitude, spatial variability, and ecological implications of these inputs into the ocean. This study compiles and standardizes observational datasets from published sources to provide a cross-substance synthesis of atmospheric concentrations, deposition fluxes, seasonal patterns, and ecological risks. The analysis covers major substance categories, including nutrients, trace metals, microplastics, POPs and other emerging pollutants. The novelty of this work lies in its cross-pollutant approach and the integration of seasonal dynamics, particularly for winter deposition. Global results show widespread deposition across the world’s oceans, with consistently elevated concentrations in densely populated coastal regions and detectable levels even in remote areas, underscoring the role of long-range transport. Our analysis reveals pronounced winter peaks in regions like the Bohai Sea and the Baltic Sea, highlighting a critical but often overlooked seasonal window. Strong nearshore-to-offshore gradients across most substances indicate dominant influences from coastal anthropogenic emissions. Ecological risk assessment using the Risk Quotient method suggests that risks are generally low but spatially heterogeneous, with hotspots in regions of intensive human activity. Overall, this synthesis highlights the importance of atmospheric pathways in shaping marine substance distributions and emphasizes the need for improved monitoring and modeling to better quantify episodic deposition processes under future environmental change.

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Early cotton topping increases peanut yield without sacrificing cotton yield through reducing interspecific competition under intercropping - Junjun Nie; Yanan Li; Zhenhuai Li; Shizhen Xu; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Lin Sun; Jianlong Dai; Yanjun Zhang; Hezhong Dong (Field Crops Research, 2026)

Plant‐Induced Transcriptional Plasticity Diverges Between Generalist and Specialist Herbivores - Jun Wu; Zhimou Lin; Guomeng Li; Wenyuan Yu; Yangzhi Zhang; Yishuo Kou; Pengshuai Peng; Tingfen He; Yu Wang; Shuai Zhan; Jean‐Christophe Simon; Saskia A. Hogenhout; et al. (Molecular Ecology, 2026)
Most herbivores are specialised on particular host plants but some are generalists that can exploit distinct hosts. Generalists may have evolved adaptive transcriptional plasticity to cope with the defences of the different hosts. However, the fundamental differences in plant‐induced transcriptional plasticity between generalists and specialists remain poorly understood. Here, we investigated transcriptional plasticity of the generalist aphid Myzus persicae and two specialist aphids, Brevicoryne brassicae and Rhopalosiphum padi , by transferring them between Brassica napus (a host for B. brassicae but not for R. padi ) and Zea mays (a host for R. padi but not for B. brassicae ), both suitable hosts for M. persicae . Generalist and specialist aphids exhibited transcriptional plasticity coordinately in response to different plant species, but their gene expression patterns often diverged. Generalist aphids attenuate the activation or even suppress salicylic acid (SA) signalling in host plants, whereas specialist aphids provoke it in nonhost plants. SA signalling had limited effects on gene expression in the generalist aphids, but significantly shaped transcriptional responses of the specialists. These findings underscore the fundamental differences in plant‐induced transcriptional plasticity between generalists and specialists and highlight the critical role of plasticity directionality in insect adaptation.

Combining hydrologic, chemical, and geophysical deep learning-based inversion for heterogeneous aquifer structure identification - Yuzhou Xia; Chuanjun Zhan; Zhenxue Dai; Jichun Wu; Xiaoying Zhang; Huichao Yin; Lin Zhu; Jiahe Yan; Zihao Wang; Mohamad Reza Soltanian; Kenneth C. Carroll (Journal of Hydrology, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

Environmental glyphosate exposure compromises sperm quality in mice by impairing acrosome biogenesis via GOLPH3-mediated golgiphagy - Yu-Long Ren; Kai Chen; Yue Li; Yan-Zhan Jia; Hao Wang; Lin Wang (Journal of Hazardous Materials, 2026)

Synergistic enhancement of bisphenol A photodegradation by BiOCl via nitrite-induced charge separation and reactive oxygen species generation: A dual role for nitrite in pollutant degradation and transformation - Zengkai Fu; Zili Lin; Junle Jian; Siling Zhang; Fengyuan Zhang; Yanfang Wang; Yunshuang He; Linsheng Liu; Yishun Wang; Hongda Zhan; Zheng Hu; Ping Chen; et al. (Journal of Environmental Chemical Engineering, 2026)

Model based decision making for efficient drip irrigation strategy of maize in arid northwestern China-A case study in Bayannur district - Yingjian Cao; Ming Zhan; Hang Xiong; Lin Chen; William D. Batchelor; Bowen Yang; Bo Chen; Lijun Li (Field Crops Research, 2026)

Impact of precipitation pH of hydrated ferric oxide on calcium-enhanced phosphate adsorption from water - Yaling Xie; Jianwei Lin; Yanhui Zhan (Chemical Engineering Journal, 2026)

Confined antisolvent precipitation enables efficient drug encapsulation in microgels for effective gouty arthritis therapy - Lumin Yang; Jinhui Lin; Shuxian Wang; Zhenyang Wei; Xiaolong Zhan; Mingyu Zhu; Yaping Ding; Wei Li (Chemical Engineering Journal, 2026)

Different light quality combinations promote adventitious shoot and adventitious root regeneration of Fraxinus mandshurica - Meihan Lin; Shangzhu Gao; Qiuju Jing; Jiawei Yan; Mengfan Zhao; Yaguang Zhan; Ying Xin; Fansuo Zeng (Trees, 2026)

Control of phosphorus release from sediment by multiple applications of lanthanum-modified palygorskite in the presence of suspended particulate matter input - Chunyu Tian; Jianwei Lin; Yanhui Zhan (Applied Clay Science, 2026)

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Electrochemical detection and electro-Fenton degradation of fipronil via Fe/Ni-BTC/MS-derived NiFe2O4@C core-shell catalyst - Yu-Qing Zhan; Cheng-Guo Liu; Jia-Jia Kou; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Journal of Cleaner Production, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Adverse drug-event detection using the tree-based scan statistics (TreeScan) and comparison with common mining methods: new user, propensity score-matched cohorts - Hailong Li; Houyu Zhao; Hongbo Lin; Peng Shen; Lingli Zhang; Siyan Zhan (European Journal of Clinical Pharmacology, 2026)

The flavor properties of Amadori rearrangement products and their potentials in flavor replication of plant-based meat analogs: a review - Huan Zhan; Wenjing Xin; Yang Deng; Tao Lin; Qingshan Shen; Khizar Hayat; Yanli Ma; Yuduan Diao (Critical Reviews in Food Science and Nutrition, 2025)

Interannual variability of summertime cross-isobath exchanges in the northern South China Sea: ENSO and riverine influences - Yunping Song; Yuxin Lin; Peng Zhan; Zhiqiang Liu; Zhongya Cai (Ocean Science, 2025)
This study, combining long-term observations and high-resolution simulations, investigates the interannual variability of summer shelf circulation in the Northern South China Sea (NSCS) from 2000 to 2022. We elucidate the responses of NSCS shelf circulation to ENSO and Pearl River Estuary (PRE) freshwater runoff, revealing distinct spatial and mechanistic signatures. During El Niño years, a pronounced sea level anomaly dipole forms between the central and southern South China Sea, intensifying northward geostrophic currents in the southern basin and modulating Kuroshio intrusions. Simultaneously, an amplified PRE plume extends eastward to the 100 m isobath, markedly reducing nearshore salinity. Analysis of depth-integrated vorticity equations indicates that the pressure gradient force – driven by the joint effect of baroclinicity and bottom relief (JEBAR) and bottom pressure gradients – governs NSCS circulation variability. In coastal regions, cross-isobath velocity anomalies are primarily controlled by bottom stress curl and nonlinear vorticity advection, whereas JEBAR dominates offshore dynamics beyond the 100 m isobath. During El Niño summers, bottom density anomalies generate positive cross-isobath velocity anomalies through JEBAR, partially offset by negative anomalies from altered vertical stratification, sustaining a meandering shelf current. These results highlight the interplay of regional and remote forcings, advancing understanding of NSCS hydrographic dynamics.

Regulation of sub-Tg solid-state surface crosslinking of reactive polyarylene ether substrate into loose nanofiltration membranes for dyes desalination - Libo Hao; Junni Xie; Lin Pan; Xingbao Yang; Qimeng Ran; Fengfan Gong; Gaolei Zhan; Dongsheng Wang; Xiaobo Liu; Kun Jia (Water Research, 2025)

Significantly improved antibiotics removal and material utilization in novel electrodialysis integrated with nanostructured carbon microspheres - Xincheng Ji; Haoming Chen; Hongfei Zhang; Yuanming Guo; Jizhong Meng; Xinmin Zhan; Liwen Xiao; Lin Shi (Water Research, 2025)

People-centered low-carbon transition: Revealing the synergy between urban low-carbon development and resident’s welfare improvement in China - Wentao Wang; Dezhi Li; Bingqian Zhan; Zirui Li; Jieyu Su; Mingchao Lin (Sustainable Cities and Society, 2025)

Hydrodynamic performance analysis and model prediction of an underwater high-speed towed body - Pengfei Xu; Meijie Cao; Hailong Lin; Zhan Wang; Yan Kai; Jianye Su; Runnan Hui; Ji Tian (Ocean Engineering, 2025)

Real-time simulation for deep-sea mining system with sea trial validation - Lin Huang; Shuqing Wang; Wencheng Liu; Yuankun Sun; Ying Li; Xuewu Hong; Mingqiang Xu; Lianjin Jiang; Fang Xu; Yuanhe Li; Hai Wu; Chi Zhan (Ocean Engineering, 2025)

Efficient leaching of Li from coal fly ash and application of leaching residue for removal of Cu(ii) from wastewater: New waste-to-value approach - Zhan Ding; Lin Li; Kaiyun Yang; Chang Liu (Minerals Engineering, 2025)

Immobilization of phosphorus in sediment-water system by hydrous iron oxide and hydrous iron oxide/calcite mixture under feed input condition - Lingui Li; Yanhui Zhan; Jianwei Lin (Journal of Environmental Sciences, 2025)

Curcumin-loaded electrospun nanofiber film based on polyvinyl alcohol and myofibrillar protein for active packaging of strawberry - Junchao Huang; Zhiyu Li; Zijia Zhan; Jingzhao Feng; Zhijie Zheng; Yijing Wu; Shoukai Lin; Qibiao Weng; Jianyi Wang; Jie Yang; Yuting Tian (Food Packaging and Shelf Life, 2025)

Shading-induced canopy cooling alleviates waterlogging damage during flowering by disrupting heat synergism in field-grown cotton - Yanjun Zhang; Yabin Yuan; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Suppressing Jahn-Teller distortion and accelerating ion kinetics via heterostructure engineering for stable aqueous zinc-ion batteries - Xiudong Chen; Xusen Chen; Xihao Lin; Dongmei Qi; Jin-Hang Liu; Yan Huang; Changchao Zhan; Hang Zhang; Yun Gao; Yao Xiao (Chemical Engineering Journal, 2025)

Nanoconfined enzymatic cascade strategy for highly efficient synthesis of D-allulose - Kan Zhan; Anni Bao; Suhai Zhang; Liang Chen; Yichen Wan; Keke Hou; Jian Hao; Lin Chaoping; Zhiyong Sun; Renchao Zheng; Yuguo Zheng (Chemical Engineering Journal, 2025)

MOF-derived core-shell MnFe2O4@C bifunctional material: Electrochemical sensing and synergistic electro-Fenton degradation of clothianidin - Jia-Jia Kou; Yu-Qing Zhan; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Chemical Engineering Journal, 2025)

CO2-mediated SEI engineering via Li2C2O4 pre-lithiation: A dual-functional strategy for high-stability SiOx/Gr anodes - Lifan Wang; Peng Han; Lin Zhang; Cong Zhong; Min Chen; Ruixiang Li; Yiheng Wu; Zhengping Zuo; Xindong Wang; Xuefeng Wang; Chun Zhan; Guicheng Liu (Chemical Engineering Journal, 2025)

Synchronous pre-lithiation at 3.5 V from lithium oxalate via micro-galvanic cells in LiFePO4 batteries - Lifan Wang; Peng Han; Lin Zhang; Xindong Wang; Chun Zhan; Guicheng Liu (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

Micro‐Faunal and Edaphic Controls on Microbial Carbon Cycling Across Primary and Secondary Successional Trajectories - Lei Du; Roland Bol; Chengwei Tu; Xiaolei Sun; Ruyi Luo; Qinghua Liu; Lin Luo; Juan Zhan; Chunying Yin; Biao Zhu; Xueyong Pang; Nicolas Fanin (Global Change Biology, 2025)
The accumulation of microbial‐derived organic carbon in soils during long‐term vegetation succession represents a key pathway for long‐term soil carbon stabilization. Yet, the role of soil microfauna in regulating microbial carbon dynamics remains poorly understood, particularly across divergent successional trajectories (primary vs. secondary successional gradients). We investigated nematode‐microbe interactions influencing carbon dynamics in primary (glacial retreat) and secondary (post‐disturbance) successional chronosequence on the eastern Qinghai‐Tibet Plateau, to identify context‐dependent mechanisms underpinning soil carbon formation and dynamics. Both successional types displayed an ‘S‐shaped’ trajectory of carbon dynamics, initially rising from early to intermediate stages, declining subsequently, then increasing again in late stages, with microbial necromass (quantified by amino sugars) dominating the carbon pool, especially in later stages. In primary succession, characterized by nutrient limitation and slower soil development, nematode‐mediated shifts in microbial community composition and functional gene expression, particularly reductions in growth‐related and decomposition genes, enhanced microbial turnover and necromass accumulation. In contrast, in phosphorus‐limited soils of secondary succession, where nutrient availability and disturbance history play a larger role, declining omnivorous nematodes modulated microbial gene expression to enhance carbon fixation and constrain decomposition under phosphorus‐rich conditions. Soil pH consistently acted as the primary abiotic factor influencing microbial communities across both successional sequences, explaining up to 29% of variation in microbial gene profiles. These findings position microbial necromass accumulation as a central pathway for carbon sequestration and identify nematodes as context‐dependent regulators of microbial carbon processing. Our study underscores the need to integrate both soil microbial and faunal dynamics, along with key physicochemical properties, into ecosystem models to improve predictions of carbon‐climate feedbacks across successional landscapes.

Application of Interprofessional Sequential Simulation Teaching Mode in Standardized Training of Radiation Oncology Residents - Hai-Zhen Yi; Xiao guo Cai; Wei Lv; Jin-Jing Chen; Zhan Lin (Journal of Cancer Education, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Effects of artificial and natural sweeteners on host metabolic health: A double-edged sword - Huimin Xue; Xiping Kang; Kexin Hong; Yunxiao Gao; Yunyu Tang; Yuchen Lin; Xiangjun Liu; Weidong Huang; Jicheng Zhan; Yilin You (Food Research International, 2025)

Platform compounds from lignocellulosic biomass by thermochemical methods: conversion control and chemical insights - Xiuming Jiang; Peilong Li; Zhan Ding; Bingfeng Lin; Xinyi Li (Chemical Engineering Journal, 2025)

Effects of Angelica sinensis polysaccharides on growth performance, antioxidant capacity, immune response, intestinal microbiota, and liver transcriptome in Mauremys mutica - Zike Yan; Jingu Shi; Kaijie Lin; Yuhan Li; Yutian Zhan; Mingzuo Gao; Hongyao Zhang; Shuyu Han; Jingzhen Liang (Aquaculture International, 2025)

Ganodermanic acid, a new steroidal compound derived from the marine fungus Aspergillu s sp. ZJUT223 - Youmin Ying; Xiaoxiao Chen; Shijie Zhan; Si Yang; Jinli Liu; Weiguang Shan; Yuhao Lin; Rong Wang (Natural Product Research, 2025)

A full-ring mechanical model of shield tunnels considering detailed joint configurations - Si-Qi Yang; Huai-Na Wu; Hong-Zhan Cheng; Dong-Lin Feng; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Oleic acid inhibits the proliferation, invasion, and migration of tongue squamous cell carcinoma cells under high glucose conditions through S100A9-HK2/PKM2-SOD2 signaling pathway - Yujie Ma; Runqiang Liu; Juan Zhan; Yihan Lai; Sicheng Li; Wei Wang; Yisen Shao; Lin Jiang (Tissue and Cell, 2025)

Defect-engineered graphene driven mercury oxidation in coal-fired flue gas via in-situ electro-Fenton catalysis - Xin Tong; Changxian Yang; Minsong Lin; Xinxing Zhan; Lingyun Zhou; Yadian Xie; Juan Tian; Gaixia Zhang; Shuhui Sun (Journal of Environmental Chemical Engineering, 2025)

Enhancement of aromatics selectivity in waste LLDPE with HZSM-5@MCM-41 Core-Shell catalysts synthesized by One-Step hydrothermal method - Huaping Lin; Yuejin Zhan; Vasilevich Sergey Vladimirovich; Bilainu Oboirien; Fanghua Xie; Qingang Xiong; Yefeng Zhou (Fuel, 2025)

Mechanistic insights into cross-modal aroma-taste interactions mediating sweetness perception enhancement in Fu brick tea - Zhihui Hu; Amr M. Bakry; Lin Shi; Ping Zhan; Wanying He; Walaa A.M. Eid; Hussein Ferweez; Yahya S. Hamed; Hesham A. Ismail; Honglei Tian; Peng Wang (Food Chemistry, 2025)

Mechanism of earthworm coelomic fluid inhibits multidrug-resistant bacteria and blocks resistance transmission - Lihan Lin; Jingwen Luo; Zhan Li; Hongan Guo; Tao Liu; Xiaojie Sun; Meiyan Xing (Environmental Pollution, 2025)

Habitat suitability assessment and prediction using a physiological species distribution model based on whole-genome genotyping and microclimate data - Bing-Xian Liu; Liang Zhang; Zhan-Wei Zhao; Lin-Xuan Ma; Xiao-Nie Lin; Ming-Ling Liao; Yun-Wei Dong (Estuarine, Coastal and Shelf Science, 2025)

Highly flexible Janus fabric based on TPU spraying and laser processing for personal thermal-wet management - Zixuan Xu; Yulun Wu; Shuqiang Min; Lin Hu; Tonghuan Zhan; Heng Wang; Yan Yuan; Haojun Luo; Yichen Tang; Bing Xu (Chemical Engineering Journal, 2025)

Control of phosphorus release from sediment by lanthanum carbonate-modified bentonite (LCBT) alone and in combination with Myriophyllum aquaticum: comparison of LCBT with lanthanum-modified bentonite and iron/aluminum co-modified calcite, and efficiency, mechanisms, and environmental safety of LCBT-Myriophyllum aquaticum combination - Xinyi Wang; Jianwei Lin; Yanhui Zhan (Journal of Soils and Sediments, 2025)

Characterizing the capability of public DEMs for mapping global floodplain bathymetry - Yaling Lin; Chenyu Fan; Kai Liu; Lingyang Liu; Xinyuan Deng; Pengju Xu; Pengfei Zhan; Xuefei Fu; Chunqiao Song (Journal of Hydrology, 2025)

Simultaneous detection of 12 estrogens in poultry meat and blood via ultrasonic extraction and GC–MS: Implications for emerging hormone exposure and health risk assessment - Can-yuan Lin; Ze-hua Liu; Dong-hao Luo; Xiao-zhan Wang; Jian Gong; Jin-yi Sun; Zhi Dang (Food Chemistry, 2025)

“Zombie” cell drug delivery system: A novel strategy for the treatment of cancer and inflammation-related diseases - Zhouru Wang; Wenjing Yang; Danhua Liu; Peihong Lin; Rui Gao; Zhen Ma; Qiao Wang; Zhan Tang; Jie Fang; Wenying Yu (Chemical Engineering Journal, 2025)

Polarization induced by electric field electro-physically strengthened the proton-coupled electron transfer to promote electrotrophic methanogenesis - Yanwei Liu; Lin Xiao; Zuli Pan; Ouru Zhan; Yabin Gong; Bo Song; Yifeng Shou; Qilin Yu; Yaobin Zhang (Chemical Engineering Journal, 2025)

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

Flash: Dual-gradient filtering membranes enable ultra-fast plasma separation - Xianchang Wu; Hui Niu; Tonghuan Zhan; Yulun Wu; Ping Qiao; Lin Hu; Bing Xu (Analytica Chimica Acta, 2025)

Superconducting phase interference effect in momentum space - Bo Zhan; Qiang Gao; Runze Chi; Yiwen Chen; Lin Zhao; Dingshun Lv; Xingjiang Zhou; Tao Xiang (Science Bulletin, 2025)

Denitrification dominates nitrate attenuation and nitrous oxide effluxes under water table fluctuations - Lin Zhang; Helin Wang; Xiaohan Liu; Hongbin Zhan; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Yanfeng Liu; Ping Li (Journal of Hazardous Materials, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Long-term exposure to air pollution and esophageal cancer incidence: A large-scale prospective cohort study - Xuwei Tang; Chanchan Hu; Zhifeng Lin; Yulan Lin; Xiaoxu Xie; Weilin Chen; Jianwen Wang; Joshua Ye; Zhijian Hu; Zhi-Ying Zhan (Environmental Research, 2025)

Enhanced phase-transfer kinetics achieved by atomic iron catalysts on hard carbon toward low-temperature sodium-ion batteries - Xinyi Qian; Ziling Wu; Jianan Gu; Yanli Wang; Xiaomin Cheng; Jing Zhang; Hongzhen Lin; Jian Wang; Liang Zhan; Yongzheng Zhang (Chemical Engineering Journal, 2025)

Chitosan/oxidized cellulose composite nanofiber sponges: a rapid and effective hemostasis strategy for non-compressible hemorrhage - Zhan Zhang; Zhiyuan Lin; Chenglong Yu; San Ieng Lei; Lu Wang; Fujun Wang; Jing Gao; Wenbo Meng (Carbohydrate Polymers, 2025)

A fine-resolution ventilation performance spatial model at pedestrian-level based on wind tunnel studies for high-density neighborhoods - Shi Yin; Yujia Zhang; Tao Lin; Yueyang He; Tingzhou Liu; Wei Liao; Qiaosheng Zhan; Sam Wong; Wenbo Lai; Edward Ng; Yiqiang Xiao (Building and Environment, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Evaluation of the Effect of Floating Treatment Wetlands Planted with Sesuvium portulacastrum on the Dynamics of Dissolved Inorganic Nitrogen, CO2, and N2O in Grouper Aquaculture Systems - Shenghua Zheng; Man Wu; Jian Liu; Wangwang Ye; Yongqing Lin; Miaofeng Yang; Huidong Zheng; Fang Yang; Donglian Luo; Liyang Zhan (Journal of Marine Science and Engineering, 2025)
Aquaculture expansion to meet global protein demand has intensified concerns over nutrient pollution and greenhouse gas (GHG) emissions. While floating treatment wetlands (FTWs) are proven for water quality improvement, their potential to mitigate GHG emissions in marine aquaculture remains poorly understood. This study quantitatively evaluated the dual capacity of Sesuvium portulacastrum FTWs to (a) regulate dissolved inorganic nitrogen (DIN) and (b) reduce CO2/N2O emissions in grouper aquaculture systems. DIN speciation (NH4+, NO2−, NO3−) and CO2/N2O fluxes of six controlled ponds (three FTW and three control) were monitored for 44 days. DIN in the FTW group was approximately 90 μmol/L lower than that in the control group, and the water in the plant group was more “oxidative” than that in the control group. The former groups were dominated by NO3−, with lower dissolved inorganic carbon (DIC) and N2O concentrations, whereas the latter were dominated by NH4+ during the first 20 days of the experiment and by NO2− at the end of the experiment, with higher DIC and N2O concentrations on average. Higher primary production may be the reason that the DIC concentration was lower in the plant group than in the control group, whereas efficient nitrification and uptake by plants reduced the availability of NH4+ in the plant group, thereby reducing the production of N2O. A comparison of the CO2 and N2O flux potentials in the plant group and control group revealed that, in the presence of FTWs, the CO2 and N2O emissions decreased by 14% and 36%, respectively. This showed that S. portulacastrum FTWs effectively couple DIN removal with GHG mitigation, offering a nature-based solution for sustainable aquaculture. Their low biomass requirement enhances practical scalability.

Simulation and experimental verification of cooling thermal performance of vertical tube downflow composite evaporative cooling tower - Tu Aimin; Lin Zhongxuan; Zhan Xuefeng; Yin Jiying; Liu Shijie; Zhu Dongsheng (International Journal of Refrigeration, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Ecological impacts of treated effluent on multitrophic biodiversity and their interactions - Wei Xiong; Ting Chen; Xun Du; Lin Hou; Yiyong Chen; Jing-Long Han; Aibin Zhan (Environmental Research, 2025)

Performance of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to eccentric compression - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2025)

Boosted polysulfides conversion in Li-S battery by atomic bimetallic catalysts: Deciphering the roles of metal sites - Xingrun Huang; Qingyuan Luo; Yizhen Tang; Zhan Lin; Chao Chen (Chemical Engineering Journal, 2025)

Regulation of electrode surface microenvironment by porous ion transport layer for High-Efficiency CO2 electrochemical reduction to ethylene - Hao-Yan Shi; Yan-Xin Chen; Yi-Hu Pu; Hai-Long Wang; Yi-Zhan Xie; Xin-Zhi Tian; Yang Yang; Ao-Sheng She; Wen Chen; Wei-Hua Yang; Xiu-Mei Lin; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Standing crop and size structure of phytoplankton are strongly regulated by the turbidity maximum in the macrotidal Qiantang River estuary-Hangzhou Bay - Lin Zhan; Yuanli Zhu; Chaoxiang Xu; Wei Du; Zhi Yang; Yulu Jiang; Kangning Jia; Ping Du; Chenhua Han; Wei Huang; Jiangning Zeng; Zhibing Jiang (Journal of Oceanology and Limnology, 2025)

Control of phosphorus release from sediment by the combined use of Elodea nuttallii, hydrous ferric oxide, zeolite and calcite: Efficiency, mechanism and response of bacterial communities - Xunxin Liu; Yanhui Zhan; Jianwei Lin (Journal of Environmental Sciences, 2025)

The Impact of Standardized Training Resident on Pain Management in Patients with Advanced Lung Cancer - Hai-Zhen Yi; Wei Lv; Jin-Jing Chen; Zhan Lin (Journal of Cancer Education, 2025)

Quantum cooling engine fueled by quantum measurements - Dengke Qu; Kunkun Wang; Lei Xiao; Zhongliang Wang; Xiang Zhan; Haiqing Lin; Peng Xue (Science Bulletin, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Salidroside alleviates doxorubicin-induced hepatotoxicity via Sestrin2/AMPK-mediated pyroptotic inhibition - Nan Wang; Zhengshan Gao; Honghong Zhan; Lin Jing; Fancheng Meng; Min Chen (Food and Chemical Toxicology, 2025)

Extracellular polymers substances towards the toxicity effect of Microcystis flos-aquae under subjected to nanoplastic stress - Jianhuang Su; Jiahui Lin; Wenlu Zhan; Jianjie Li; Xiuxian Dong; Tingting Zhang; Zaixian Yang; Zhuanxi Luo; Peiyong Guo (Environmental Pollution, 2025)

Eggshell-inspired heterogeneous bilayer paper window with selective gas permeability for preserving fresh produce - Lin Peng; Junyu Chen; Yongye Chen; Azadeh Nilghaz; Xueyan Yun; Xiaofang Wan; Huanhuan Zhan; Junfei Tian (Chemical Engineering Journal, 2025)

Regulating local oxygen covalence and interrupting transition metal migration path by multisite doping to stabilize Li-rich layered cathodes - Ziyang Liang; Wenzhao Huang; Gesong Huang; Xiaola Li; Yuqing Liu; Boyang Zhang; Shuxing Wu; Chenyu Liu; Zhan Lin; Dong Luo (Chemical Engineering Journal, 2025)

Two-photon polymerization 3D printing of biomimetic microstructures for functionalizing surfaces to inhibit bacterial growth - Wentao Zhu; Fang-Yi Huo; Lei-Ming Cao; Zi-Zhan Li; Qian Zhu; Rongxiang He; Bolei Chen; Yong Liang; Bo Cai; Hong He; Lin-Lin Bu; Ligang Hu (Chemical Engineering Journal, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

Integrated transcriptomics and metabolomics uncover metabolites and pathways in American bullfrog (Aquarana catesbeiana) response to Elizabethkingia miricola infection - Peikui Yang; Jiawei Lin; Jude Juventus Aweya; Qiongjun Zhao; Yuzhong Zheng; Xianghui Zou; Yanjie Sun; Yaqun Liu; Shixiong Zhan (Aquaculture, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Enhanced adsorption performances of chlorine doped copper-based materials for hydrogen sulfide at room temperature - Biliang Lin; Weiyan Zhu; Changbo Ai; Qingyun Long; Minghao Wu; Huian Zhan; Ning Zhao; Yifan Zhang; Yong Wang (Journal of Environmental Chemical Engineering, 2025)

T-2 toxin induces cardiac fibrosis by causing metabolic disorders and up-regulating Sirt3/FoxO3α/MnSOD signaling pathway-mediated oxidative stress - Lichun Qiao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jingming Zhan; Feidan Deng; Miaoye Bao; Huifang He; Xinyue Wen; Huan Deng; Xining Wang; Yujie He; et al. (Journal of Environmental Sciences, 2025)

Impact of the root ratio of herbs and shrubs on the soil shear strength of collapsing walls in Benggang - Fang Shuai; Hua Wang; Fang Ha; Yuanyuan Zhan; Haoming Shen; Bo Ma; Yue Zhang; Jinshi Lin; Yanhe Huang; Fangshi Jiang (Journal of Mountain Science, 2025)

Causes and Geomorphological Effects of Relative Sea Level Movement in the Yellow River Delta During the Last 2000 Years - Qing Wang; Chao Zhan; Teng Su; Hongyuan Shi; Longsheng Wang; Lin Zeng; Xianbin Liu; Buli Cui (Journal of Ocean University of China, 2025)

Nitrogen-removed organic matters from cyanobacterial decomposition promote the release of nitrogen from lake sediment - Mengmeng Wang; Yixuan Zhan; Chenyu Wang; Xiaohua Song; Lin Gan; Hao Lu; Liuyan Yang (Environmental Science and Pollution Research, 2025)

Analytical solution for longitudinal equivalent bending stiffness of large-diameter shield tunnels with internal structures - Tao Chen; Huai-Na Wu; De-Sai Guo; Xin-Xin Yang; Hong-Zhan Cheng; Lin-Song Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Discrepancies between radiocarbon and optically stimulated luminescence ages in eolian deposits on the northeastern Tibetan Plateau since 14 kyr - Fangming Zeng; Tao Zhan; Jianlan Luo; Zhenqing Zhang; Lin Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Study on hydrocarbon retention and expulsion of kerogen based on centrifugal swelling method - Tian Liang; Feng Zhu; Zhao-Wen Zhan; Xiao-Hui Lin; Yan-Rong Zou; Ping’an Peng (Organic Geochemistry, 2025)

Electrochemically driven inactivation of harmful cyanobacteria assisted with the visible light photocatalyst of CeO2-Fe3O4-CQDs - Ze Zhang; Hua Chai; Jiehao Zhan; Boyang Liu; Yinhan Lin; Wendi Zhang; Lihua Cui; Rongliang Qiu; Zhujian Huang (Journal of Environmental Management, 2025)

High electrocatalytic activity of crystallization-modulated ordered PtCu3/C nanoalloy catalysts for oxygen reduction reaction - Xiaomei Li; Linfeng Fu; Lin Cao; Lihui Lei; Xinxing Zhan; Changgang Hu; Xin Tong; Juan Tian (Chemical Engineering Journal, 2025)

Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2025)

Comparative experimental study on the thermal and energy performance of photovoltaic and green roofs in hot-humid climates - Qiaosheng Zhan; Yuchan Ma; Zhenghao Lin; Shi Yin; Yiqiang Xiao (Building and Environment, 2025)

Novel Silicon-Based Fluorescent Nanocomposite Drug Carriers for Natural Compound Delivery in Melanoma Treatment - Fei Gao; Lei Li; Linbo Liu; Guangshuai Li; Jianan Zhang; Wang Zhan; Wenjian You; Xia Lin; Yun Liu; Jiayao Wang; Denglin Chen (Journal of Fluorescence, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Theoretical estimations of carbon geological storage capacities in the deep aquifer in Songliao Basin: Insights from spatial stochastic simulation - Zhijian Sun; Lin Zhang; Wanli Xue; Chong Zhang; Hongbin Zhan; Yanfeng Liu (Journal of Environmental Management, 2025)

Application of 3-D inversion of AMT data in exploration of concealed nonmetallic deposits: A Case Study on the Huashitou Mountain fluorite deposit in Beishan metallogenic belt, China - Jianhui Hu; Liuyang Xu; Yaotian Yin; Xu Jia; Ping Qi; Zhan Liang; Peng Su; Cheng Liu; Weidong Tang; Long Chen; Yanzhou Wang; Lin Liu (Journal of Applied Geophysics, 2025)

Novel one-step method to construct gellan gum-zein core-shell structured starch beads for regulating starch digestion - Zhiwei Lin; Weixian Li; Chengcheng Zhang; Linjie Zhan; Xiaoyang He; Yang Qin; Qingjie Sun; Na Ji (Food Chemistry, 2025)

Performance and calculation of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to bending - Zhan-Shuo Liang; Lin-Hai Han; Pu Wang (Engineering Structures, 2025)

Combined application of Bacillus amyloliquefaciens and sodium selenite promotes tea seedling growth and selenium uptake by regulating the rhizosphere bacterial community - Liu Li; Lin Luo; Juan Zhan; Ali Raza; Chunying Yin (Biology and Fertility of Soils, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Occurrence characteristics, removal efficiencies and potential health risks of typical viruses in rural domestic sewage: A review - Yingming Zhu; Su Xu; Yu Zhou; Xuesong Guo; Yunping Han; Jun Zhan; Lin Li; Junxin Liu (Journal of Water Process Engineering, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Tensile Bearing Performance and Mechanical Transfer Mechanism of Coal-Rock Composite Anchor Bodies Under Different Height Ratios of Rock to Coal - Pandong Zhang; Lin Gao; Xiaohe Wang; Yinwei Wang; Xinyu Zhan; Fanghao Zhao (Rock Mechanics and Rock Engineering, 2025)

Epigenetic Modifications as Novel Therapeutic Strategies of Cancer Chemoprevention by Phytochemicals - Hui-Hsia Hsieh; Min-Zhan Kuo; I-An Chen; Chien-Ju Lin; Victor Hsu; Wei-Chun HuangFu; Tien-Yuan Wu (Pharmaceutical Research, 2025)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

A metabolic roadmap of waxy corn flavor - Jingyun Luo; Chunmei He; Shijuan Yan; Chenglin Jiang; An Chen; Kun Li; Yongli Zhu; Songtao Gui; Ning Yang; Yingjie Xiao; Shenshen Wu; Fajun Zhang; et al. (Molecular Plant, 2024)

Unraveling size-dependent catalytic activity of monolithic alginate hydrogels for PMS activation and ciprofloxacin removal - Jie Lin; Yunxiong Zeng; Xingyu Zhan; Jingcai Xu; Xinqing Wang; Bo Hong; Xiaoling Peng; Jing Li; Hongwei Chen; Yingchun Xia (Journal of Environmental Chemical Engineering, 2024)

Integrating a high-energy activation method for the sustainable treatment of iron smelting slag, phosphogypsum, and arsenic-contaminated water - Donghui Chen; Jie Tan; Hong Li; Yanmin Lin; Fangming Nan; Qingwen Han; Wei Zhan (Journal of Environmental Chemical Engineering, 2024)

Constructing in-situ and real-time monitoring methods during soy sauce production by miniature fiber NIR spectrometers - Zhankai Zhang; Yanhua Ding; Feng Hu; Zhan Liu; Xiaodong Lin; Jiangyan Fu; Qingyu Zhang; Zhi-hong Zhang; Haile Ma; Xianli Gao (Food Chemistry, 2024)

Efficient hydrogen production from food waste leachate using single-chamber microbial electrolysis cell - Shuyue Ma; Yifan Zhang; Lingli Tu; Xin Li; Xindi Chen; Songwei Lin; Haiping Luo; Xinmin Zhan; Guangli Liu (Environmental Research, 2024)

Performance evaluation of resin wafer electrodeionization for enhanced nitrogen recovery from ammonium-containing water environment - Redae Nuguse Berhe; Yu-I Lin; Shu-Yuan Pan; Min Zhan; Hyunook Kim (Chemical Engineering Journal, 2024)

Investigation of ponatinib metabolism and drug-drug interactions with lycopene and shikonin in vitro and in vivo - Jie Chen; Fengsheng Hong; Hailun Xia; Yuxin Shen; Xiaohai Chen; Hualu Wu; Guanyang Lin; Ruanjuan Zhan (Chemico-Biological Interactions, 2024)

Selective regulation of products for guaiacol hydrodeoxygenation by adjusting type and acidity of supports - Min Lin; Daxin Jiang; Yuhao Yan; Lulu Zhan; Xianliang Song; Rui Li; Yulong Wu (Bioresource Technology, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Resting state EEG delta-beta amplitude-amplitude coupling: a neural predictor of cortisol response under stress - Xiaoyu Wang; Li Lin; Lei Zhan; Xianghong Sun; Zheng Huang; Liang Zhang (Cognitive Neurodynamics, 2024)

Circ-Luc7l Absence Attenuates Diabetic Nephropathy Progression by Reducing Mesangial Cell Excessive Proliferation, Inflammation, and Extracellular Matrix Accumulation via Mediating the miR-205-5p/Tgfbr1 Pathway - Zhan Fang; Dan Wang; Fang Sun; Jing Chang; Dong Yuan; Shuhua Lin; Jian Teng (Biochemical Genetics, 2024)

Super-large diameter slurry shield tunnel encountering boulder formation: Detection, treatment and data analysis - Wei-Hong Yang; Dong Su; Xing-Tao Lin; Zhi-Jia Lv; Zhan-Hu Yao; Hui Li; Ya-Zhou Zhang; Xiang-Sheng Chen (Transportation Geotechnics, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Efficient degradation of ciprofloxacin by innovative VUV/BN system: Kinetics, mechanism and toxicity assessment - Hongda Zhan; Zili Lin; Lingrong Chen; Zhenjun Xiao; Dezhu Liu; Yishun Wang; Zhihong Chen; Zhenchao Li; Zengkai Fu; Linsheng Liu; Zihong Xu; Shuyue Chen; et al. (Journal of Water Process Engineering, 2024)

Improving peanut growth and cadmium phytoextraction capacity by inoculating Bacillus megaterium and Trichoderma harzianum - Jie Xiong; Dongsheng Zou; Jianguo Kang; Yingying Mo; Lin Li; Likun Zhan; Qingdan Wu; Zhihua Xiao (Journal of Environmental Management, 2024)

Passive protection of chicken egg yolk immunoglobulin (IgY) against Streptococcus agalactiae infection in Nile tilapia (Oreochromis niloticus) - Linpeng Zhang; Yucong Hong; Kaihui Sun; Shuyan Zhao; Yanhan Bai; Shiyi Yang; Junjie Tao; Fei Shi; Fanbin Zhan; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Corrigendum to ‘Machine-learning-based corrections of CMIP6 historical surface ozone in China during 1950–2014’ [Environ. Pollut. 357 (2024) 124397] - Yuanxi Tong; Yingying Yan; Jintai Lin; Shaofei Kong; Zhixuan Tong; Yifei Zhu; Yukun Yan; Zhan Sun (Environmental Pollution, 2024)

Enhanced global dust counteracted greenhouse warming during the mid- to late-Holocene - Shiwei Jiang; Xin Zhou; Jasper F. Kok; Qifan Lin; Yonggang Liu; Tao Zhan; Yanan Shen; Zhibo Li; Xuanqiao Liu; Anze Chen; Luo Wang; Wen Chen; et al. (Earth-Science Reviews, 2024)

Significant enhancement of photocatalytic H2 evolution and tetracycline degradation by CdO nanosheets-modified UiO-66-NH2 nanoparticles - Lin Zhang; Qingru Zeng; Yimin Liu; Zhan Wang; Yuezhou Wei; Deqian Zeng (Chemical Engineering Journal, 2024)

Robust self-healing ion-conductive interlocking dual-network binder based on gradient dynamic bonding for advanced SiO anodes in Li-Ion batteries - De He Weng; Liu Zhen Wu; Zi Feng He; Dong Yu Zhu; Yuan Li; Bole Ma; Qiyu Liu; Liheng Chen; Zhan Lin; Xueqing Qiu (Chemical Engineering Journal, 2024)

Carbon emissions and drivers across five urban agglomerations of China: Comparison between the 12th and 13th Five-Year Plan periods - Jingjing Si; Yongjian Li; Congyu Zhao; Hongbin Zhan; Shizhuang Zhang; Lin Zhang (Stochastic Environmental Research and Risk Assessment, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

The oncogenic role of EIF4A3/CDC20 axis in the endometrial cancer - Yan Lin; Lili Kong; Yiting Zhao; Fengguang Zhai; Ziqing Zhan; Yuxuan Li; Zheng Jingfei; Yan Chunhong; Xiaofeng Jin (Journal of Molecular Medicine, 2024)

Influence of Ocean Current Features on the Performance of Machine Learning and Dynamic Tracking Methods in Predicting Marine Drifter Trajectories - Huan Lin; Weiye Yu; Zhan Lian (Journal of Marine Science and Engineering, 2024)
Accurately and rapidly predicting marine drifter trajectories under conditions of information scarcity is critical for addressing maritime emergencies and conducting marine surveys with resource-limited unmanned vessels. Machine learning-based tracking methods, such as Long Short-Term Memory networks (LSTM), offer a promising approach for trajectory prediction in such scenarios. This study combines satellite observations and idealized simulations to compare the predictive performance of LSTM with a resource-dependent dynamic tracking method (DT). The results indicate that when driven solely by historical drifter paths, LSTM achieves better trajectory predictions when trained and tested on relative trajectory intervals rather than the absolute positions of individual trajectory points. In general, LSTM provides a more accurate geometric pattern of trajectories at the initial stages of forecasting, while DT offers superior accuracy in predicting specific trajectory positions. The velocity and curvature of ocean currents jointly influence the prediction quality of both methods. In regions characterized by active sub-mesoscale dynamics, such as the fast-flowing and meandering Kuroshio Current and Kuroshio Current Extension, DT predicts more reliable trajectory patterns but lacks precision in detailed position estimates compared to LSTM. However, in areas dominated by the fast but relatively straight North Equatorial Current, the performance of the two methods reverses. The two methods also demonstrate different tolerances for noise and sampling intervals. This study establishes a baseline for selecting machine learning methods for marine drifter prediction and highlights the limitations of AI-based predictions under data-scarce and resource-constrained conditions.

An analytical model of longitudinal joints in the segmental lining of shield tunnels with considering geometric nonlinearity - Dong-Lin Feng; Huai-Na Wu; Ren-Peng Chen; Si-Qi Yang; Hong-Zhan Cheng (Tunnelling and Underground Space Technology, 2024)

Hotspot–subduction zone interactions and their resource effects at ∼120 Ma on the central Tibetan Plateau - Jia-Wei Bai; Jian-Jun Fan; Ye Zhan; Bo-Chuan Zhang; Si-Lin Sun; Yu-Jie Hao (Lithos, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Suppression of phosphorus release from sediment by Vallisneria natans combined with iron- and zirconium-modified bentonites: Effectiveness, mechanism, and response of sedimentary microbial communities - Tianyu Guo; Jianwei Lin; Yanhui Zhan (Journal of Environmental Chemical Engineering, 2024)

Hygrothermal resilience of typical lightweight steel-framed wall assemblies in hot-humid areas under future climate uncertainty - Qiaosheng Zhan; Sihan Xue; Shi Yin; Zhenghao Lin; Yukai Zou; Yiqiang Xiao (Energy and Buildings, 2024)

Synergistic enhancement of UASB reactor for leachate treatment using Fe2O3 nanomodified pumice and ozone oxidation - Yu-Zhou Yang; Yong Zhang; Yu Zhan; Jia-Qi Liu; Chuan-Chuan Yan; Ying Zhang; Hua-Lin Zhang (Chemical Engineering Journal, 2024)

Assembly of 3D printed N-doped biochar as impeller with CaCO3 as sacrificial pore generator for enhanced dye adsorption - Zining Zhou; Kaiji Xu; Changyong Li; Jianbin Lin; Juanjuan Bian; Kang Sun; Jianchun Jiang; Shu-Feng Zhou; Guowu Zhan (Chemical Engineering Journal, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Voltage recovery from frozen microbial fuel cells in the laboratory and outdoor field reactors - Chunyang Lin; Haoran Liang; Xiaojing Yang; Jingjing Zhan; Qiao Yang (Science of The Total Environment, 2024)

Machine-learning-based corrections of CMIP6 historical surface ozone in China during 1950–2014 - Yuanxi Tong; Yingying Yan; Jintai Lin; Shaofei Kong; Zhixuan Tong; Yifei Zhu; Yukun Yan; Zhan Sun (Environmental Pollution, 2024)

Global abnormal precipitation 18O depletion during late/post monsoon season - Huiwen Guo; Hongxi Pang; Shuangye Wu; Tao Xu; Sebastian G. Mutz; Zhaojun Zhan; Wen Lin; Wangbin Zhang; Shugui Hou (Earth and Planetary Science Letters, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

A short linear glucan nanocomposite hydrogel formed by in situ self-assembly with highly elastic, fatigue-resistant and self-recovery - Jinling Zou; Zhiwei Lin; Linjie Zhan; Yang Qin; Qingjie Sun; Na Ji; Fengwei Xie (Carbohydrate Polymers, 2024)

Down-regulation of RTEL1 Improves M1/M2 Macrophage Polarization by Promoting SFRP2 in Fibroblasts-derived Exosomes to Alleviate COPD - He-Ping Xu; Feng Zhan; Hong Wang; Jie Lin; Huan Niu (Cell Biochemistry and Biophysics, 2024)

Can incorporating image resolution into neural networks improve kidney tumor classification performance in ultrasound images? - Haihao He; Yuhan Liu; Xin Zhou; Jia Zhan; Changyan Wang; Yiwen Shen; Haobo Chen; Lin Chen; Qi Zhang (Medical & Biological Engineering & Computing, 2024)

Sealing solid agar in serum bottles for rapid isolation and long-term preservation of chemoautotrophic ammonia-oxidizing bacteria - Jiajie Wu; Manjun Zhan; Lingling Yuan; Yueyue Zhu; Weitie Lin; Jianfei Luo (Water Research, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Relationship between photochromism and persistent luminescence in barium-magnesium silicates - Rujun Yang; Long Chen; Cunjian Lin; Honghui Huang; Zishuang Wu; Chenhan Zhan; Yixi Zhuang; Rong-Jun Xie (Chemical Engineering Journal, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Rapid warming and increasing moisture levels in the Qaidam Basin - Fangming Zeng; Xiying Zhang; Tao Zhan; Zhenqing Zhang; Lin Chen; Lingkang Chen; Ming Ji (Theoretical and Applied Climatology, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

Resveratrol ameliorates cyprodinil-induced zebrafish cardiac developmental defects as an aryl hydrocarbon receptor antagonist - Ruyu Zhan; Fushan Zhou; Chaoyang Liu; Chuanchang Chen; Mingmei Li; Dongqin Huang; Naying Zheng; Tingting Lin; Zhenghong Zuo; Chengyong He; Xintan Chen (Environmental Science and Pollution Research, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Enhancing stand establishment and yield formation of cotton with multiple drip irrigation during emergence in saline fields of Southern Xinjiang - Jianlong Dai; Zhengpeng Cui; Yanjun Zhang; Lijie Zhan; JunJun Nie; Jianqiang Cui; Dongmei Zhang; Shizhen Xu; Lin Sun; Bing Chen; Hezhong Dong (Field Crops Research, 2024)

Three thousand years of Hg pollution recorded in mangrove wetland sediments from South China - Minqi Chen; Bigyan Neupane; Xuan Zhan; Ting Liu; Zhanyi Lin; Changjun Gao; Claudio Zaccone; Kunshan Bao (Environmental Research, 2024)

Steric interaction of iridium sites towards efficient oxygen and hydrogen evolution - Weibin Chen; Lei Li; Zhan Lin (Chemical Engineering Journal, 2024)

Geochemical characteristics of the modern Yellow River Delta sediments and their response to evolution of the sedimentary environment - Liwei Meng; Longsheng Wang; Qing Wang; Jiawen Zhao; Guiye Zhang; Chao Zhan; Xianbin Liu; Buli Cui; Lin Zeng (Frontiers in Marine Science, 2024)
Introduction Sedimentary evolution and river channel changes of large river delta (e.g. Huang River, Changjiang River) in response to environmental changes have been one of the key issues in global change research. Methods This study reconstructed sedimentary environment changes in the modern Yellow River Delta (YRD), based on grain size and elemental chemical analysis of two short cores (YDC and YDG) from the southern region of the Qing 8 course delta of the modern YRD. Results The results indicated that the cores YDC and YDG sediment were dominated by silt (58.47% and 67.6%, respectively) with varied grain-size variations and poor sediment sorting. The cores YDC and YDG sediments are both predominantly composed of the major element SiO2, and have an average content of 55.53% and 58.45%, respectively. The R-mode factor analysis showed the content of chemical substances of core sediments was controlled by three factors: grain size, sedimentary provenance, and marine sedimentary dynamics. Discussion Before the diversion of the Yellow River to the Qing 8 course in 1996, the two cores sediment were mainly sources from the Yellow River, and both cores were in the delta-front sedimentary environment under weak hydrodynamic conditions. After the Yellow River was diverted to the Qing 8 course, the cores YDC and YDG experienced significant erosion under the nearshore strong waves and tides. And then the sedimentary environment of the YRD changed from siltation to erosion. The results of the study would be helps to further our understanding of the changes in sediment grain size and geochemical element characteristics in the Yellow River estuary, and reveal the evolution of its sedimentary environment.

Atmosphere-dependent combustion of Ganoderma lucidum biomass toward its enhanced transformability into green energy - Hanlin Cao; Hongda Zhan; Jianying Qi; Sen Lin; Mingzhong Ren; Jiayu Liang; Fatih Evrendilek; Yao He; Jingyong Liu (Environmental Science and Pollution Research, 2024)

Direct shear behaviors of excavated clay reinforced with geocomposite drainage layer encapsulated in thin sand layers - Lin-Jie Wang; Hui Xu; Jian-Wen Qian; Jin-Nan Wang; Liang-Tong Zhan (Environmental Science and Pollution Research, 2024)

Genome-wide sequencing reveals geographical variations in the thermal adaptation of an aquaculture species with frequent seedling introductions - Liang Zhang; Zhan-Wei Zhao; Lin-Xuan Ma; Yun-Wei Dong (Science of The Total Environment, 2024)

Chronology by luminescence and radiocarbon on core sediments from the northeastern pearl river plain and implications for delta process - Penghui Lin; Xian Hu; Weiqi Zhan; Yucong Chen; Ken Ling; Bingfa Zhi; Hongwei Li; Zhongping Lai (Quaternary Geochronology, 2024)

Control of phosphorus release from sediment by hydrous zirconium oxide/magnesium hydroxide composite: Effectiveness, mechanism and microbial response - Chunniu Sheng; Jianwei Lin; Yanhui Zhan (Journal of Environmental Chemical Engineering, 2024)

Do plants directly absorb nitrogen derived from deposition of wildfire smoke? - Ziyan Huang; Xiaoyu Zhan; Yuanfan Ma; Pingxin Zhao; Mulualem Tigabu; Guangyu Wang; Haichuan Lin; Futao Guo (Forest Ecology and Management, 2024)

Comparison of the regulatory effects of flavonoids and saponins from Eclipta prostrate on insulin resistance in HepG2 cells - Li Yang; Xiao-mei Zhan; Si-bo Zhao; Xi-lin Xu; Jian-guo Jiang; Wei Zhu (Food Bioscience, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Surface atom rearrangement enabling graphitic carbon nitride/sodium alginate gel monolith for ultrafast completely photodegrading ciprofloxacin under visible light - Xingyu Zhan; Zhilong Zhang; Jie Lin; Jingcai Xu; Xinqing Wang; Bo Hong; Yingchun Xia; Yunxiong Zeng (Chemical Engineering Journal, 2024)

Integration of anaerobic digestion and electrodialysis for methane yield promotion and in-situ ammonium recovery - Jizhong Meng; Lin Shi; Yuansheng Hu; Zhongzhong Wang; Zhenhu Hu; Xinmin Zhan (Bioresource Technology, 2024)

A short-term of starvation improved the antioxidant activity and quality of African catfish (Clarias gariepinus) - Fanbin Zhan; Qingqing Li; Huiwen Feng; Ruikang Lin; Weiming Liang; Li Lin; Zhendong Qin (Fish Physiology and Biochemistry, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Salinity fronts shape spatial patterns in Zooplankton distribution in Hangzhou Bay - Yepeng Xu; Yiqi Wang; Lin Zhan; Yijun Ou; Kangning Jia; Ming Mao; Xuyu Zhu; Zhibing Jiang; Yuanli Zhu; Wei Huang; Ping Du; Jiangning Zeng; et al. (Acta Oceanologica Sinica, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Effects of airflow disturbance from a multi-rotor unmanned aerial vehicle on fruit tree frost protection - Baiyu Qiao; Lingxiao Wang; Hu Han; Zhan Huang; Yongda Lin; Zongkai Jia; Hongyuan Nie; Xiongkui He; Yajia Liu (Biosystems Engineering, 2024)

Potential pathogenic microorganisms in rural wastewater treatment process: Succession characteristics, concentration variation, source exploration, and risk assessment - Jun Zhan; Su Xu; Yingming Zhu; Yunping Han; Lin Li; Junxin Liu; Xuesong Guo (Water Research, 2024)

Highly modified cephalotane-type diterpenoids from Cephalotaxus fortunei var. alpina and C. sinensis - Zhan-Peng Ge; Jin-Biao Xu; Peng Zhao; Mai Xiang; Yu Zhou; Ze-Min Lin; Jian-Ping Zuo; Jin-Xin Zhao; Jian-Min Yue (Phytochemistry, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Dissolved organic matter accelerates microbial degradation of 17 alpha-ethinylestradiol in the presence of iron mineral - Huan He; Min Shi; Xiaoxia Yang; Juhong Zhan; Yanting Lin; Ziwei Guo; Zhicheng Liao; Chaochao Lai; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Environmental Sciences, 2024)

Enhanced catalytic performance and N2 yield of Ag/CeO2 catalyst by Cu modification for NVOCs removal - Xiaohan Guo; Fanshun Lin; Meixingzi Gao; Qiguang Dai; Wangcheng Zhan; Li Wang; Yun Guo; Aiyong Wang; Yanglong Guo (Chemical Engineering Journal, 2024)

Packing blockage and power generation of constructed wetland coupled microbial fuel cell systems using biochar as electrode and filler with different ratios - Hongyu Xin; Rui Yang; Chunyang Lin; Jingjing Zhan; Qiao Yang (Chemical Engineering Journal, 2024)

Electrochemical oxidation processes based on renewable energy towards carbon neutrality: Oxidation fundamentals, catalysts, challenges and prospects - Yan Yan; Bing Lin; Liehui Zhang; Yingying Wang; Hailong Zhang; Hongpeng Zheng; Taigang Zhou; Yingqing Zhan; Zongxue Yu; Yun Kuang; Junlei Tang (Chemical Engineering Journal, 2024)

Late Cenozoic uplift of the Liupan Mountains: Evidence from the Neogene loess deposits - Zhilin He; Yansong Qiao; Zhengtang Guo; Chaoqin Chen; Long Chen; Yang Fu; Ye Yang; Yanxia Liang; Xinru Lin; Guoqiao Xiao; Tao Zhan (Science China Earth Sciences, 2024)

Optimization of canopy resistance models for estimating evapotranspiration on summer maize in a semi-arid condition of China - Cun Zhan; Lu Zhao; Yaling Zhang; Xinbei Lin; Gang Zhou; Zetao Zheng (Irrigation Science, 2024)

Control of phosphorus release from sediment by iron/aluminum co-modified zeolite: efficiency, mechanism, and response of microbial communities in sediment - Jiayang Zhou; Jianwei Lin; Yanhui Zhan (Environmental Science and Pollution Research, 2024)

Tree barriers height information extraction under power line based on watershed segmentation and local maximum algorithm - Yan Li; Lv Zhou; Xue Lin Wen; Tai Ying Wu; Mian Lan; Di Zhang; Yi Zhan Zhao; Peng De Lai (International Journal of Remote Sensing, 2024)

In-situ reactivation and reuse of micronsized sulfidated zero-valent iron using SRB-enriched culture: A sustainable PRB technology - Yanduo Yang; Chungeng Zhan; Yu Li; Jiajia Zeng; Keyue Lin; Jianliang Sun; Feng Jiang (Water Research, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Comparative study by microwave pyrolysis and conventional pyrolysis of pharmaceutical sludge: Resourceful disposal and antibiotic adsorption - Yifan Zhou; Fawei Lin; Zhongqian Ling; Mingxiu Zhan; Guangxue Zhang; Dingkun Yuan (Journal of Hazardous Materials, 2024)

Controllable lignin valorization to value-added aromatic chemicals by a UV-assisted ternary heterogeneous photo-fenton catalytic system - Fen Wang; Lin Zhang; Zhiping Wu; Wenbo Peng; Peng Zhan; Lishu Shao; Hui Wang; Yan Qing; Hanxue Lin; Quan Wei; Na Liu; Zhaohui Tong (Fuel, 2024)

Highly water-soluble and biocompatible hyaluronic acid functionalized upconversion nanoparticles as ratiometric nanoprobes for label-free detection of nitrofuran and doxorubicin - Abdur Raheem Aleem; Rihui Chen; Tonghua Wan; Wei Song; Chuyan Wu; Xue Qiu; Qiuqiang Zhan; Kuncheng Xu; Xin Gao; Tianci Dong; Xiang Chen; Lin Yu; et al. (Food Chemistry, 2024)

Response of air pollution to meteorological conditions and socioeconomic activities associated to the COVID-19 outbreak in the Yangtze River Economic Belt - Jingjing Si; Lin Zhang; Shizhuang Zhang; Yongjian Li; Zhixin Zhang; Ziqi He; Ying Chen; Hongbin Zhan (Atmospheric Environment, 2024)

PCSK9 regulates myocardial ischemia–reperfusion injury through parkin/pink1-mediated autophagy pathway - Guangwei Huang; Hailong Bao; Peng Zhan; Xiyang Lu; Zonggang Duan; Xinlin Xiong; Muzhi Lin; Bing Wang; Hongxin An; Luanda Xiahou; Haiyan Zhou; Zhenhua Luo; et al. (Molecular & Cellular Toxicology, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Natural product-derived ferroptosis mediators - Yi-Li Chen; Lin-An Xiong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Ammonium enrichment, nitrate attenuation and nitrous oxide production along groundwater flow paths: Carbon isotopic and DOM optical evidence - Lin Zhang; Zhixin Zhang; Xin Huang; Jingwei Zhang; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Hongbin Zhan (Journal of Hydrology, 2024)

Study of life cycle assessment: Transforming microalgae to biofuel through hydrothermal liquefaction and upgrading in organic or aqueous medium - Shaomin Zhou; Min Lin; Xi Zhang; Lulu Zhan; Rui Li; Yulong Wu (Journal of Cleaner Production, 2024)

Physical drivers of Noctiluca scintillans (Dinophyceae) blooms outbreak in the northern Taiwan Strait: A numerical study - Zhonghao Lin; Peng Zhan; Jianping Li; Jun Sasaki; Zhongfeng Qiu; Chun Chen; Shuangyan Zou; Xiaotong Yang; Haifeng Gu (Harmful Algae, 2024)

Unveiling the aromatic intricacies of Wuyi Rock Tea: A comparative study on sensory attributes and odor-active compounds of Rougui and Shuixian varieties - Daoliang Wang; Zhibin Liu; Xiaoye Lan; Cainan Wang; Wensong Chen; Sijia Zhan; Yaqian Sun; Weiying Su; Chih-Cheng Lin; Wei Liu; Yuan Liu; Li Ni (Food Chemistry, 2024)

Trussed concrete-filled steel tubular hybrid structures subjected to axial compression: Performance and design calculation - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Fine-scale monitoring of lake ice phenology by synthesizing remote sensed and climatologic features based on high-resolution satellite constellation and modeling - Jie Tong; Yaling Lin; Chenyu Fan; Kai Liu; Tan Chen; Fanxuan Zeng; Pengfei Zhan; Linghong Ke; Yongnian Gao; Chunqiao Song (Science of The Total Environment, 2024)

Enhancing the NOx storage and hydrothermal stability of Pd/SSZ-13 passive NOx adsorbers by regulating the Al distributions - Yinan Wang; Xuteng Zhao; Ting Chen; Zuwei Zheng; Rijing Zhan; He Lin (Fuel, 2024)

Mechanochemical synthesis of Ni/MgO dual functional materials at room temperature for CO2 capture and methanation - Zhan-Kuo Guo; Su Gao; Shu-Xiang Xiang; Jin-Peng Wang; Guo-Cui Mao; Hui-Lin Jiang; Bao-Xia Dong; Yun-Lei Teng (Chemical Engineering Journal, 2024)

Temperature–Controlled hydrothermal hydrogenation of palmitic acid to alkanol or alkanes over Co@CN–x catalysts derived from ZIF–67 - Min Lin; Daxin Jiang; Yuhao Yan; Xiaoxian Li; Lulu zhan; Xianliang Song; Rui Li; Yulong Wu (Chemical Engineering Journal, 2024)

Investigations in mutation breeding and culturing media by Xanthophyllomyces dendrorhous - Qibin Lin; Xiaoru Wang; Liang Zhang; Yingyu Shu; Yurou Zhang; Ruoting Zhan; Kui Wang (Biocatalysis and Agricultural Biotechnology, 2024)

Quantifying uncertainty: The benefits of removing snow cover from remote sensing time series on the extraction of climate-influenced grassland phenology on the Qinghai–Tibet Plateau - Nan Li; Pei Zhan; Yaozhong Pan; Lin Qiu; Jingjing Wang; Wenxuan Xu (Agricultural and Forest Meteorology, 2024)

Identifying the function of the PI3K‐AKT pathway during the pathogenic infection of Macrobrachium rosenbergii - Fanbin Zhan; Shichun Zhou; Fei Shi; Qingqing Li; Li Lin; Zhendong Qin (Journal of Fish Diseases, 2024)
The phosphoinositide‐3‐kinase/protein kinase b (PI3K‐Akt) pathway is a signalling pathway based on protein phosphorylation and can be activated by a wide range of factors. To investigate the function of the PI3K‐AKT signalling pathway in antibacterial immunity, we analysed the gene expression level of three key factors ( PI3K , AKT and FoxO ) and innate immune factors in immune tissues at different time points after Vibrio parahaemolyticus and Staphylococcus aureus infection. Tissues analysis showed that PI3K , AKT , and FoxO were expressed at high levels in the intestinal, hemocytes and hepatopancreas. Moreover, the expression levels of PI3K , AKT and FoxO can be regulated postinfection by different pathogens. In hemocytes and the intestine, V . parahaemolyticus infection was found to regulate the levels of PI3K , AKT , and FoxO more rapidly; however, an S . aureus infection regulated the levels of these factors more rapidly in the hepatopancreas and gills. Analysis showed that V . parahaemolyticus and S . aureus infection caused changes in the gene expression level of crustin , caspase 3 and NF‐κB . Therefore, PI3K‐AKT regulates the downstream immune pathway differentially in different immune tissues and participates in the regulation of cell apoptosis and the inflammatory response by activating caspase and NF‐κB, respectively, following infection with V . parahaemolyticus and S . aureus .

A coupled model applied to complex river–lake systems - Qi Zhang; Chesheng Zhan; Yueling Wang; Haoyue Zhang; Zhonghui Lin (Hydrological Sciences Journal, 2024)

Fertilizer recovery from source-separated urine by evaporation with a combined process of dehumidification and the addition of absorbent resin supplement - Xiaojing Lin; Zhan Jin; Shunfeng Jiang; Zhiquan Wang; Suqing Wu; Ke Bei; Min Zhao; Xiangyong Zheng (Water Research, 2024)

The anti-cancer drug candidate CBL0137 induced necroptosis via forming left-handed Z-DNA and its binding protein ZBP1 in liver cells - Jun Li; Miao Tang; Ruo-Xian Ke; Pei-Lin Li; Zhi-Guo Sheng; Ben-Zhan Zhu (Toxicology and Applied Pharmacology, 2024)

Rare 7,9′-dinorlignans with neuroprotective activity from the roots of Lindera aggregata (Sims) Kosterm - Qian-Qing Liu; Lin-An Xiong; Jia-Yu Qian; Ting-Ting Gong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Combination effects of ultrasound and citral nanoemulsion against Shigella flexneri and the preservation effect on fresh-cut carrots - Luyi Song; Hui Yang; Shuai Cheng; Zhen Zhang; Lechi Zhang; Ruiying Su; Yuxi Li; Xiangjun Zhan; Baowei Yang; Lin Lin; Chao Shi (Food Control, 2024)

The brominated flame retardant tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) as well as hexabromocyclododecane lead to lipid disorders in mice - Xuan-Yue Chen; Yuan-Yuan Li; Lin Lv; Yi-Ming Xiong; Zhan-Fen Qin (Environmental Pollution, 2024)

Atomic-level surface modification of ultrathin Bi2WO6 nanosheets for boosting photocatalytic CO2 reduction - Lulu Zhao; Huilin Hou; Lin Wang; Chris R. Bowen; Jinguo Wang; Ruifang Yan; Xiaoqiang Zhan; Hongli Yang; Man Yang; Weiyou Yang (Chemical Engineering Journal, 2024)

Influence of solar activity and large-scale climate phenomena on extreme precipitation events in the Yangtze River Economic Belt - Yi Wu; Lin Zhang; Zhixin Zhang; Jingyun Ling; Shiqi Yang; Jingjing Si; Hongbin Zhan; Wenling Chen (Stochastic Environmental Research and Risk Assessment, 2024)

Obtainment and Inoculation of Acinetobacter pittii Strain JJ-2, and Combined Action with Plants for Formaldehyde and CO2 Removal: A Research Study - Jiaochan Zhong; Silan Chen; Shujie Lin; Yinjuan Jia; Han Li; Ting Zhan; Jian Li (Current Microbiology, 2024)

Occurrence, behavior and fate of liquid crystal monomers in municipal wastewater - Yuting Zhan; Qianqian Jin; Huiju Lin; Danyang Tao; Lok Yung Law; Jiaji Sun; Yuhe He (Water Research, 2023)

Immobilization of phosphorus in water-sediment system by iron-modified attapulgite, calcite, bentonite and dolomite under feed input condition: Efficiency, mechanism, application mode effect and response of microbial communities and iron mobilization - Siyu Jin; Jianwei Lin; Yanhui Zhan (Water Research, 2023)

Hydraulic circulation technology remediates the contaminated groundwater with petroleum hydrocarbon: Evidence from laboratory and field tests - Zhan Chen; Yu-Lin Wu; Tao Li; Yi-Xiang Wang; Ling-Kang Xuan; Shi-Feng Lu (Journal of Cleaner Production, 2023)

Industrial air pollution and low birth weight in New Mexico, USA - Xi Gong; Yanhong Huang; Jenny Duong; Shuguang Leng; F Benjamin Zhan; Yan Guo; Yan Lin; Li Luo (Journal of Environmental Management, 2023)

An electroconductive hydrogel with injectable and self-healing properties accelerates peripheral nerve regeneration and motor functional recovery - Zhenwei Yi; Fangke Zhan; Yijia Chen; Ran Zhang; Haodong Lin; Liming Zhao (Chemical Engineering Journal, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Fe-pillared montmorillonite functionalized chitosan/gelatin foams for efficient removal of organic pollutants by integration of adsorption and Fenton degradation - Anrong Yao; Yafang Wang; Jincheng Yu; Siyao Tian; Yifei Zhan; Hongjiang Liao; Jianwu Lan; Shaojian Lin (Carbohydrate Polymers, 2023)

Pathological observation and transcriptomic analysis of thymus injury in PRRSV-infected piglets - Naying Su; Zhengdan Lin; Xi Liu; Xiuxiu Sun; Xinxin Jin; Helong Feng; Cunlin Zhan; Xueying Hu; Changqin Gu; Wanpo Zhang; Guofu Cheng (Veterinary Research Communications, 2023)
The thymus, the central immune organ in mammals, plays an important role in immune defense. Porcine reproductive and respiratory syndrome virus (PRRSV) infection in piglets can cause thymus injury and immunosuppression. However, the mechanisms of thymus injury remain unknown. This study was aimed at investigating the specific manifestations of thymus injury through the construction of a PRRSV-infected piglet model and histopathological observation. In this study, fourteen 40-day-old PRRSV-free piglets were randomly divided into two groups, eleven of which were intramuscularly injected with 3 mL of PRRSV WUH3 virus suspension (10 6 PFU /mL) in the infection group, and three of which were sham-inoculated with 3 mL of RPMI-1640 medium in the control group. Clinical necropsy and samples collection were performed on day 8 after artificial infection. With the Illumina platform, the transcriptomes of piglet thymus tissues from infected and control piglets were sequenced to explore the relationships of differentially expressed genes (DEGs) and signaling pathways with thymus injury. The immune organs of PRRSV-infected piglets were severely damaged. The histopathological findings in the thymus indicated that PRRSV infection was associated with a large decrease in lymphocytes, cell necrosis and cell apoptosis; an increase in blood vessels and macrophages; thymic corpuscle hyperplasia; and interstitial widening of the thymic lobules. The transcriptomic analysis results revealed that the Gene Ontology functions of DEGs were enriched primarily in biological processes such as angiogenesis, regulation of angiogenesis and positive regulation of cell migration. Moreover, greater numbers of blood vessels and macrophages were observed in the thymus in PRRSV-infected than control piglets. KEGG pathway enrichment analysis revealed that the DEGs were significantly enriched in the Toll-like receptor signaling pathway, chemokine signaling pathway, IL-17 signaling pathway and TNF signaling pathway. The expression of TLR8, IRF5, the chemokines CCL2, CCL3L1 and CCL5; and their receptors CCR1, CCR2 and CCR5 was significantly up-regulated in PRRSV infection, thus suggesting that these cytokines were associated with the pathological processes of thymus injury.

A shared role of the myocardin-family transcriptional coactivators in cardiomyocyte maturation - Yuxuan Guo; Yangpo Cao; Blake D. Jardin; Neil Mazumdar; Congting Guo; Luzi Yang; Junsen Lin; Zhan Chen; Qing Ma; Mingming Zhao; Erdan Dong; William T. Pu (Science China Life Sciences, 2023)

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Flood risk assessment of check dams in the Wangmaogou watershed on the Loess Plateau of China - Ze-chao Gao; Peng Shi; Zhan-bin Li; Peng Li; Lu-lu Bai; Yi Jia; Lin Cui (Journal of Mountain Science, 2023)

Experiment and numerical study on combustion characteristics of low-nitrogen burners - Yi Liu; Youchang Zhao; Lin Zhang; Jiayong Wu; Jinjie Feng; Chengman Zhou; Yanru Shen; Xi Zhan; Kexin Dong; Qi Wang (Fuel, 2023)

Insights into the surface Structure-Sensitive photocatalytic oxidation of gaseous toluene on Pd/TiO2 catalysts - Cong Wu; Qinglong Liu; Yu Zhan; Wei Tan; Xiaoqian Wei; Qing Tong; Haiqin Wan; Lin Dong (Chemical Engineering Journal, 2023)

ATP-responsive and functionalized framework nucleic acid for synergistic radio-immunotherapy - Yuxin Zhang; Yuxi Zhan; Chenchen Mao; Guo Li; Yuxuan Zhao; Ye Chen; Yunfeng Lin (Chemical Engineering Journal, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Preparation, characterization, and evaluation of the antitumor effect of kaempferol nanosuspensions - Wen He; Junfeng Zhang; Jiale Ju; Yinghua Wu; Yuxi Zhang; Lin Zhan; Chenchen Li; Yanli Wang (Drug Delivery and Translational Research, 2023)

The Relationship Between Cortical Morphological and Functional Topological Properties and Clinical Manifestations in Patients with Posttraumatic Diffuse Axonal Injury: An Individual Brain Network Study - Fuqing Zhou; Lin Wu; Long Qian; Hongmei Kuang; Jie Zhan; Jian Li; Gerald L. Cheung; Aimin Ding; Honghan Gong (Brain Topography, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Advances in high performance anion exchange membranes: Molecular design, preparation methods, and ion transport dynamics - Ximin Chen; Yingqing Zhan; Junlei Tang; Xulin Yang; Ao Sun; Bing Lin; Fei Zhu; Hongshan Jia; Xianzhang Lei (Journal of Environmental Chemical Engineering, 2023)

Terminal removal at first square enhances vegetative branching to increase seedcotton yield at low plant density - Junjun Nie; Lin Sun; Lijie Zhan; Xue Li; Wenting Hou; Yanjun Zhang; Weijiang Li; Dongmei Zhang; Zhengpeng Cui; Zhenhuai Li; Shizhen Xu; Jianlong Dai; et al. (Field Crops Research, 2023)

Advanced Progression for the Heterogeneity and Homeostasis of Intestinal Stem Cells - Minqiong Sun; Zhenya Tan; Keqiong Lin; Xiaofei Li; Jicheng Zhu; Li Zhan; Hong Zheng (Stem Cell Reviews and Reports, 2023)

Genome-wide identification and functional characterization of borneol dehydrogenases in Wurfbainia villosa - Xiaojing Lin; Linxuan Huang; Huilin Liang; Chen Hou; Xuli Ling; Yuanxia Chen; Peng Yang; Qingwen Wu; Haiying Zhao; Sirong Wu; Ruoting Zhan; Dongming Ma; et al. (Planta, 2023)

Efficient determination of scalar coupling networks by band selective decoupled 2D NMR spectroscopy - Haolin Zhan; Cunyuan Gao; Chengda Huang; Xiaoqing Lin; Yuqing Huang; Zhong Chen (Analytica Chimica Acta, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Effect of common ions aging treatment on adsorption of phosphate onto and control of phosphorus release from sediment by lanthanum-modified bentonite - Yanhui Zhan; Bo Qiu; Jianwei Lin (Journal of Environmental Management, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

Oxygen-induced dual-signal point-of-care testing aptasensor for aflatoxin B1 detection using platinum nanoparticle catalysis in visual fluorometry and gravimetry - Fang Luo; Linxiu Zhan; Ye Deng; Kun Qiao; Nan Pan; Zuquan Weng; Cuiying Lin; Bin Qiu; Zhenyu Lin (Analytica Chimica Acta, 2023)

Control of phosphorus release from sediment by hydrous zirconium oxide combined with calcite, bentonite and zeolite - Yuqian Lu; Jianwei Lin; Xugan Wu; Yanhui Zhan (Chemosphere, 2023)

Semen damage contributed over 50 % to air-pollutant-induced infertility: A prospective cohort study of 3940 men in China - Ying Guo; Qing Chen; Yu Zhan; Wenzheng Zhou; Haiyan Zhang; Niya Zhou; Huan Yang; Yi Chen; Yimeng Wang; Lei Sun; Lin Ao; Jinyi Liu; et al. (Science of The Total Environment, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Transcriptome analysis of Macrobrachium rosenbergii hemocytes in response to Staphylococcus aureus infection - Fanbin Zhan; Shichun Zhou; Fei Shi; Qingqing Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

Nighttime light perspective in urban resilience assessment and spatiotemporal impact of COVID-19 from January to June 2022 in mainland China - Yaohui Liu; Wenyi Liu; Xinyu Zhang; Yu Lin; Guoqiang Zheng; Zhan Zhao; Hao Cheng; Lutz Gross; Xiaoli Li; Benyong Wei; Fei Su (Urban Climate, 2023)

Understanding changing public transit travel patterns of urban visitors during COVID-19: A multi-stage study - Yuqian Lin; Yang Xu; Zhan Zhao; Sangwon Park; Shiliang Su; Mengyao Ren (Travel Behaviour and Society, 2023)

Long-term effects of rewetting and drought on GPP in a temperate peatland based on satellite remote sensing data - Yinying Zhou; Torsten Sachs; Zhan Li; Yuwen Pang; Junfeng Xu; Aram Kalhori; Christian Wille; Xiaoxue Peng; Xianhao Fu; Yanfei Wu; Lin Wu (Science of The Total Environment, 2023)

Influence of seasonal water-level fluctuations on depth-dependent microbial nitrogen transformation and greenhouse gas fluxes in the riparian zone - Lin Zhang; Yanfeng Liu; Menggui Jin; Xing Liang; Stefan Krause; Uwe Schneidewind; Yiming Li; Hongbin Zhan (Journal of Hydrology, 2023)

Elucidating the chemical structures of petroleum resin using solid-state 13C NMR - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Ping'’an Peng (Chemical Geology, 2023)

Effect of capping mode on control of phosphorus release from sediment by lanthanum hydroxide - Fujun Sun; Yanhui Zhan; Jianwei Lin (Environmental Science and Pollution Research, 2023)

Cytotoxicity and hemolysis of rare earth ions and nanoscale/bulk oxides (La, Gd, and Yb): Interaction with lipid membranes and protein corona formation - Yiping Feng; Jingyi Wu; Haijian Lu; Wenhao Lao; Hongda Zhan; Longyong Lin; Guoguang Liu; Yirong Deng (Science of The Total Environment, 2023)

New dimeric sesquiterpenoids from the whole plant of Artemisia sieversiana - Jun-yi Dong; Yu-xing Cai; Ya-lin Li; Yu-xin Zhang; Zhan-peng Yu; Ling-yi Kong; Jian-guang Luo (Phytochemistry Letters, 2023)

Effects of antibiotics on immunity and apoptosis on grass carp liver and hepatocytes - Fei Shi; Minshan Yao; Yao Huang; Zhilong Chen; Jin Xiao; Fanbin Zhan; Yanan Li; Li Lin; Zhendong Qin (Journal of Environmental Chemical Engineering, 2023)

The Keap1-Nrf2 signaling pathway regulates antioxidant defenses of Ctenopharyngodon idella induced by bacterial infection - Yanan Li; Zongfu Chen; Yayuan Xiao; Feng Gao; Fanbin Zhan; Zhijie Lu; Zhenpeng Huang; Xuefeng Wei; Fengping Su; Fei Shi; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2023)

Hydrochromic wood biocomposites for humidity and moisture detection - Yujie Chen; Chaozheng Liu; Zhaolun Liang; Lei Ye; Lin Liu; Zhipeng Liu; Xinhao Feng; Lloyd Donaldson; Tripti Singh; Xianxu Zhan; Jingquan Han; Qiliang Fu; et al. (Chemical Engineering Journal, 2023)

Theoretical determination method and field verification of the fracture position of the main roof of the gob-side coal-rock roadway in gently inclined coal seam - Xinyu Zhan; Lin Gao; Pengze Liu; Zhiqiang Zhao; Pandong Zhang; Ping Liu; Yongyin Wang (Bulletin of Engineering Geology and the Environment, 2023)

Bisphenol C induces developmental defects in liver and intestine through mTOR signaling in zebrafish (Danio rerio) - Jinfeng Liu; Jiebo Lin; Jiafeng Chen; Yasen Maimaitiyiming; Kunhui Su; Siqi Sun; Guankai Zhan; Chih-Hung Hsu (Chemosphere, 2023)

Combined amendment and capping of sediment with ferrihydrite and magnetite to control internal phosphorus release - Jianwei Lin; Yan Li; Yanhui Zhan; Xugan Wu (Water Research, 2023)

A temporally relaxed theory of physically or chemically non-equilibrium solute transport in heterogeneous porous media - Ying-Fan Lin; Junqi Huang; Elliot J. Carr; Tung-Chou Hsieh; Hongbin Zhan; Hwa-Lung Yu (Journal of Hydrology, 2023)

Role of roasting in the formation of characteristic aroma of wuyi rock tea - Sijia Zhan; Zhibin Liu; Weiying Su; Chih-Cheng Lin; Li Ni (Food Control, 2023)

Characterization analysis of TLR5a and TLR5b immune response after different bacterial infection in grass carp (Ctenopharyngodon idella) - Fanbin Zhan; Yanan Li; Fei Shi; Zhijie Lu; Minxuan Yang; Qingqing Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2023)

Tumor microenvironment-responsive nanosystem achieves reactive oxygen species self-cycling after photothermal induction to enhance efficacy of antitumor therapy - Yuting Peng; Lianghao Cheng; Chunyi Luo; Fuquan Xiong; Zhiping Wu; Lin Zhang; Peng Zhan; Lishu Shao; Weihua Luo (Chemical Engineering Journal, 2023)

Late Pleistocene to Holocene sedimentary history in the Pearl River Delta revealed by OSL and radiocarbon dating - Penghui Lin; Yingjin Song; Weiqi Zhan; Ruonan Tian; Zhongbo Wang; Xiaolin Xu; Lan Luo; Mahmoud Abbas; Zhongping Lai (CATENA, 2023)

A fractionation strategy of cellulose, hemicellulose, and lignin from wheat straw via the biphasic pretreatment for biomass valorization - Qiwen Zhan; Qixuan Lin; Yue Wu; Yao Liu; Xingjie Wang; Junli Ren (Bioresource Technology, 2023)

Hygrothermal performance optimization of lightweight steel-framed wall assemblies in hot–humid regions using orthogonal experimental design and a validated simulation model - Qiaosheng Zhan; Yiqiang Xiao; Lei Zhang; Zhenghao Lin; Yukai Zou; Wei Liao (Building and Environment, 2023)

Cross-sectional rainfall observation on the central-western Tibetan Plateau in the warm season: System design and preliminary results - Kun Yang; Yingying Chen; Lazhu; Changhui Zhan; Xiaoyan Ling; Xu Zhou; Yaozhi Jiang; Xiangnan Yao; Hui Lu; Xiaogang Ma; Lin Ouyang; Weihao Pan; et al. (Science China Earth Sciences, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Comparison of magnetite, hematite and goethite amendment and capping in control of phosphorus release from sediment - Jianwei Lin; Weijie Xiang; Yanhui Zhan (Environmental Science and Pollution Research, 2023)

Investigating the evolution of landscape patterns in historical subdeltas and coastal wetlands in the Yellow River Delta over the last 30 years: A geo-informatics approach - Chao Zhan; Qing Wang; Shanshan Cheng; Lin Zeng; Jiankui Yu; Cheng Dong; Xiang Yu (Frontiers in Marine Science, 2023)
Historically, the river course and coastline of the Yellow River Delta changed frequently, and many studies focused on these change trends and their driving forces. Few studies have explored the influence of historical river channels and historical coastlines on the response of modern landscape patterns. This study examines the impact of channel migration and coastline evolution on the modern landscape pattern of historical subdeltas and coastal wetlands, utilizing a combination of Geo-informatics and Remote Sensing images in 1989, 1998, 2009, and 2016. The results showed that: (1) Subdeltaic landscapes changed from 1998 to 2016, with slight changes in most landscape types in the Ancient Qing Shui Course Subdelta (AQSD), an increase in building sites by 17% in the Zhimai Course Subdelta (ZMSD), a decrease in the proportion of Phragmites/cogongrass communities by 15.8% in the Diao Kou Course Subdelta (DKSD), and domination by natural landscapes in the Modern Qing Shui Course Subdelta (MQSD). (2) Coastal wetlands also experienced changes, with an increase in cultivated land to 60% in the coastal wetlands of CWI, a decline in natural landscapes, and an increase in artificial landscapes in the coastal wetlands of CWII and CWIII, and domination by natural landscapes but an increase in salt fields and culture ponds by 3.45% in the coastal wetlands of CWIV. (3) Channel migration and coastline evolution influenced the direction of landscape succession, causing the landscape-type centroids in the entire delta to move eastward or northward. (4) Throughout the delta, the human tendency to live by rivers was observed. This was due to the availability of freshwater from these rivers, which led to the expansion of inhabited areas and man-made water bodies along the river banks. Channel migration and coastline evolution aggravated the salinization of coastal wetlands and promoted the salt industry and aquaculture in some estuaries of the Yellow River. In general, human activities play a dominant role in shaping the landscape pattern in the Yellow River Delta, but they were largely restricted to historical channel migration and historical coastline evolution.

Immune and protective effects of subunit vaccines from S-domain or P-domain in capsid protein against nervous necrosis virus in pearl gentian grouper - Tianwen Lin; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2023)

The changes of chemical molecular components in soil organic matter are associated with fungus Mortierella capitata K. - Fang Li; Lin Chen; Zhan-Hui Zhao; Yue Li; Hai-You Yu; Yi Wang; Jia-Bao Zhang; Yan-Lai Han (Soil and Tillage Research, 2023)

Insights into Lewis/Brønsted acidity of metal chlorides and solvent effect of alcohols for synthesis of γ-valerolactone by combining molecular dynamics simulations and experiments - Qiwen Zhan; Qixuan Lin; Yao Liu; Junli Ren; Libo Li; Weiying Li (Fuel, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

Advantages of aggregation-induced luminescence microspheres compared with fluorescent microspheres in immunochromatography assay with sandwich format - Xiaxia Wei; Xirui Chen; Zilong Liu; Ge Xu; Guoxin Chen; Xiangkai Lin; Wenchao Zhan; Xiaolin Huang; Yonghua Xiong (Analytica Chimica Acta, 2023)

End-member characteristics of sediment grain size in modern Yellow River delta sediments and its environmental significance - Liwei Meng; Longsheng Wang; Jiawen Zhao; Chao Zhan; Xianbin Liu; Buli Cui; Lin Zeng; Qing Wang (Frontiers in Marine Science, 2023)
Introduction The sediments of the Yellow River delta record the environmental changes in the Yellow River basin on a long time scale and are sensitive to the river diversion and sedimentary environment evolution. Methods In this study, cores YDC and YDG in the delta near the estuary of the Yellow River since 1976 were taken as the research object, and the parameterized end-member analysis model was used to analyze the grain-size data of the cores. Results The results show that: The main sediments were silty and sand (58% and 77.9%). The grain-size parameters showed opposite changes with wide grain-size ranges and mixed sizes obviously. End member 1 (EM1) and end member 2 (EM2) were composed of clay and fine silt with fine particle sizes of 0.04 mm and 9.8 mm, respectively, and were deposited under weak hydrodynamic conditions during long-distance transport along the Yellow River. End member 3 (EM3) and end member 4 (EM4) were coarse silt with mode particle sizes of 40.14 mm and 66.89 mm, respectively. These were deposited by waves and tidal currents under strong dynamic conditions. Discussion According to the channel changes and the sedimentary facies data of the modern Yellow River delta, before the Yellow River was diverted in 1996, the cores YDC and YDG were both in the estuary-front bar sedimentary environment. In 1996, the Yellow River was diverted to the Qing 8 course. Subsequently, the core YDC changed to the delta-plain sedimentary facies, and the core YDG changed to the delta-front facies. The sediment sources of the two cores changed from the Yellow River sediments to coastal sediment erosion and resuspension. The sedimentary environment changed from siltation to erosion. The results of this study are of great practical significance for estuary management and coastal engineering construction in the modern Yellow River delta and can provide a scientific basis for ecological protection and high-quality development of the Yellow River basin.

A comprehensive review on mixotrophic denitrification processes for biological nitrogen removal - Jintao Zhang; Chunzhen Fan; Min Zhao; Zhiquan Wang; Shunfeng Jiang; Zhan Jin; Ke Bei; Xiangyong Zheng; Suqing Wu; Ping Lin; Huanyi Miu (Chemosphere, 2023)

Screening and characterization of sex-specific markers by NGS sequencing in Spinibarbus hollandi with implication of XY sex determination system - Chong Han; Wenwei Huang; Suhan Peng; Jiangwei Zhou; Huawei Zhan; Lin Gui; Wenjun Li; Qiang Li (Aquaculture, 2023)

The study on the main mode of the death of red blood cells in grass carp (Ctenopharyngodon idella) - Hong Chen; Minshan Yao; Ying Tang; Lixiang Wei; Junyan Lin; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Study on the regulatory mechanism of erythropoietin in erythropoiesis in grass carp (Ctenopharyngodon idella) - Junyan Lin; Lixiang Wei; Minshan Yao; Hong Chen; Ying Tang; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

A numerical investigation of the transport process of density currents over steep slopes and its implications for subsea cable breaks - Sheng-De Tsai; Jia-Lin Chen; Wen-Yang Hsu; Wei-Zhan Tsai; Andhy Romdani (Ocean Engineering, 2023)

Transcriptome analysis of Macrobrachium rosenbergii hemocytes reveals in-depth insights into the immune response to Vibrio parahaemolyticus infection - Fanbin Zhan; Yanan Li; Fei Shi; Zhijie Lu; Minxuan Yang; Qingqing Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2023)

Total petroleum hydrocarbons and influencing factors in co-composting of rural sewage sludge and organic solid wastes - Su Xu; Jun Zhan; Lin Li; Yingming Zhu; Junxin Liu; Xuesong Guo (Environmental Pollution, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

Effect of electric field and water on Pd-based catalyst for complete oxidation of methane: Study on promotion and deactivation - Xuteng Zhao; Ting Chen; Yinan Wang; Ke Li; Reggie Zhan; He Lin (Chemical Engineering Journal, 2023)

Research on type I kerogen molecular simulation and docking between kerogen and saturated hydrocarbon molecule during oil generation - Tian Liang; Zhao-Wen Zhan; Yan-Rong Zou; Xiao-Hui Lin; Yun Shan; Ping'’an Peng (Chemical Geology, 2023)

Composition of inorganic elements in fine particulate matter emitted during surface fire in relation to moisture content of forest floor combustibles - Ziyan Huang; Yuanfan Ma; Xiaoyu Zhan; Haichuan Lin; Chenyue Zheng; Mulualem Tigabu; Futao Guo (Chemosphere, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Alleviating the self-discharge and enhancing the polysulphides conversion kinetics with LaCO3OH nanocrystals decorated hierarchical porous carbon - Yuhang Lin; Weiqiang Tang; Siyu Wu; Yongzheng Zhang; Zhenkai Kong; Chunyin Shen; Yanli Wang; Liang Zhan; Licheng Ling (Chemical Engineering Journal, 2023)

Effect of aged nanoscale zero-valent iron amendment and capping on phosphorus mobilization in sediment - Xiangtian Yang; Jianwei Lin; Yanhui Zhan (Chemical Engineering Journal, 2023)

Functionalized graphene oxide/sodium alginate beads with ion responsiveness for uranium trapping - Yu Nan; Jianli Wang; Xue Chang; Kejin Shao; Yuchen Lin; Lijuan Qian; Zhan Li; Peizhuo Hu (Carbohydrate Polymers, 2023)

SATB1/SLC7A11/HO-1 Axis Ameliorates Ferroptosis in Neuron Cells After Ischemic Stroke by Danhong Injection - Sikai Zhan; Jiayin Liang; Huiting Lin; Jiale Cai; Xinxin Yang; Hongwei Wu; Junying Wei; Shumei Wang; Minghua Xian (Molecular Neurobiology, 2023)

Associations of trace element levels in paired serum, whole blood, and tissue: an example of esophageal squamous cell carcinoma - Kexin Cao; Jingbing Zhang; Geng Wang; Xiaosheng Lin; Fulan Zhan; Kusheng Wu; Wei Tan; Hui Geng; Caixia Liu (Environmental Science and Pollution Research, 2022)

Tracing the source–sink process of fluvio-clastic materials: Magnetic records of surface sediments in the Yangtze River basin - Xianbin Liu; Jing Chen; Wei Yue; Qing Wang; Chao Zhan; Lin Zeng; Jian Song; Longsheng Wang; Buli Cui (Frontiers in Marine Science, 2022)
In this study, we collected surface sediments from the mainstream and major tributaries of the Yangtze River to systematically analyse their magnetic properties, and discuss the implications for tracing source–sink process of fluvio-clastic materials. Our results showed that the surface sediments from tributaries in the upper basin had a significantly higher content of ferromagnetic minerals and coarser grain sizes than that in the mid-lower basin. The magnetic susceptibility (χ lf ) of surface sediments from the mainstream was 34.16*10 -8 m 3 /kg at Shigu, rapidly rose to 230.56*10 -8 m 3 /kg at Yibin, and then dropped to 68.92*10 -8 m 3 /kg at the river mouth. The χ lf of Yalong River sediments in the upper basin was 276.86*10 -8 m 3 /kg, considerably higher than that of the sediments from other tributaries, and greatly contribute to the χ lf of the sediments in the mainstream, reflecting the dominant constraining role of the Emeishan basalts. The distinctive magnetic properties of the upper core sediments from Jianghan basin and the Yangtze delta closely match those of surficial river sediments of the upper Yangtze basin. This may indicate the addition of clastic materials eroded from the upper basin, resulting from the cut-through of the Three Gorges during the evolution of the Yangtze River that occurred in the late Cenozoic. Investigating the magnetic properties of the surface sediments in the Yangtze River basin can provide insights into the source–sink process of clastic materials and environmental changes.

Geomorphologic evolution of the shallow-buried abandoned Yellow River delta during the last 2000 years - Qing Wang; Lin Zeng; Chao Zhan; Xianbin Liu; Longsheng Wang; Shanshan Cheng; Buli Cui (Frontiers in Marine Science, 2022)
Different from the continuous development of many river deltas since the major Holocene transgression, the modern Yellow River delta (YRD) remained for nearly 1000 years (from 893 AD to 1855 AD) in an abandonment state, until after 1855 AD when it was buried after the Yellow River entered the sea via Lijin. In this study we used optically stimulated luminescence (OSL) dating and grain size and sedimentary facies analysis of four borehole cores, combined with an analysis of landform morphology, to reconstruct the history of the ancient abandoned YRD. The results indicate that after the delta was abandoned due to the reduced sediment supply by the Yellow River in 893 AD, a sandy coast developed under the influence of wave erosion, and offshore shell ridges were formed beyond the coastline. During the interval from the Medieval Warm Period (MWP) to the Little Ice Age (LIA), driven by climate change and storm surges, the shell ridges migrated laterally, widened and rose, while sediment accumulation in the landward-side interfluvial floodplains was relatively weak. This configuration subsequently constituted a coastal highland – plain depression system. After 1077 AD, this system, together with the abandoned delta, was eroded by the Daqing River estuary. After 1855 AD, the abandoned delta landform system was completely buried by Yellow River sediments, and the wave-controlled sandy coast was transformed to a tide-controlled silt-mud coast. We summarize these findings in the form of a geomorphic model of the evolution of the abandoned delta from the MWP to the LIA. Overall, our results highlight the geomorphic effects of the sediment-laden river delta and the response of the abandoned delta geomorphic system on the millennial timescale, and they provide a theoretical foundation for predicting the geomorphic evolution of a major river delta on different timescales, against the background of global change.

SIRT1-Enriched Exosomes Derived from Bone Marrow Mesenchymal Stromal Cells Alleviate Peripheral Neuropathy via Conserving Mitochondrial Function - Lizhen Shan; Fenfen Zhan; Detao Lin; Fabo Feng; Xinji Chen; Xiaolin Li; Di Yang (Journal of Molecular Neuroscience, 2022)

Genomic Analysis and Molecular Characteristics in Carbapenem-Resistant Klebsiella pneumoniae Strains - Suying Zhao; Xingyi Qiu; Yiting Tan; Min Xu; Xiaotong Xu; Yulai Ge; Huiling Cao; Min Li; Yuxin Lin; Zhan Zhang; Lei Li; Qian Wu (Current Microbiology, 2022)

Research progress on intervention effect and mechanism of protocatechuic acid on nonalcoholic fatty liver disease - Yunxiao Gao; Rongrong Tian; Haiyue Liu; Huimin Xue; Ruizhe Zhang; Suping Han; Lin Ji; Weidong Huang; Jicheng Zhan; Yilin You (Critical Reviews in Food Science and Nutrition, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

PDGFD switches on stem cell endothelial commitment - Weisi Lu; Peipei Xu; Boxiong Deng; Jianing Zhang; Ying Zhan; Xianchai Lin; Xiangzhong Xu; Zhaoxia Xia; Xiaoxi Yang; Xiaoling Zeng; Lijuan Huang; Bingbing Xie; et al. (Angiogenesis, 2022)
The critical factors regulating stem cell endothelial commitment and renewal remain not well understood. Here, using loss- and gain-of-function assays together with bioinformatic analysis and multiple model systems, we show that PDGFD is an essential factor that switches on endothelial commitment of embryonic stem cells (ESCs). PDGFD genetic deletion or knockdown inhibits ESC differentiation into EC lineage and increases ESC self-renewal, and PDGFD overexpression activates ESC differentiation towards ECs. RNA sequencing reveals a critical requirement of PDGFD for the expression of vascular-differentiation related genes in ESCs. Importantly, PDGFD genetic deletion or knockdown increases ESC self-renewal and decreases blood vessel densities in both embryonic and neonatal mice and in teratomas. Mechanistically, we reveal that PDGFD fulfills this function via the MAPK/ERK pathway. Our findings provide new insight of PDGFD as a novel regulator of ESC fate determination, and suggest therapeutic implications of modulating PDGFD activity in stem cell therapy.

PmliHFM: Predicting Plant miRNA-lncRNA Interactions with Hybrid Feature Mining Network - Lin Chen; Zhan-Li Sun (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Identification of serum metabolites enhancing inflammatory responses in COVID-19 - Chen-Song Zhang; Bingchang Zhang; Mengqi Li; Xiaoyan Wei; Kai Gong; Zhiyong Li; Xiangyang Yao; Jianfeng Wu; Cixiong Zhang; Mingxia Zhu; Lei Zhang; Xiufeng Sun; et al. (Science China Life Sciences, 2022)

Measuring the phase response of a seismometer using superimposed sine signals - Zhan Lin; Yuntian Teng; Bing Xue; Xinxin Ma (Journal of Seismology, 2022)

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

Two new clerodane diterpenoids and a new pyran-2-one derivative with anti-neuroinflammatory activities from Croton crassifolius - Zhi-Peng Ling; Qing Tang; Can-Jie Li; Jin-Lin Tan; Hai-Yue Zhao; Yi-Kun Hao; Zhao-Chun Zhan; Zhong-Nan Wu; Yu-Bo Zhang; Qing Zheng; Guo-Cai Wang (Journal of Natural Medicines, 2022)

In vitro adventitious shoot regeneration system for Agrobacterium-mediated genetic transformation of Fraxinus mandshurica Rupr. - Fenghui Qi; Mingshuo Tang; Wenxuan Wang; Lin Liu; Yang Cao; Tianzhong Jing; Yaguang Zhan (Trees, 2022)

Effect of application mode (capping and amendment) on the control of cadmium release from sediment by apatite/calcite mixture and its phosphorus release risk - Chi Liu; Jianwei Lin; Zhibin Zhang; Yanhui Zhan; Dazhu Hu (Environmental Science and Pollution Research, 2022)

Post-transcriptional control of bacterial nitrogen metabolism by regulatory noncoding RNAs - Yueyue Han; Chao Li; Yongliang Yan; Min Lin; Xiubin Ke; Yunhua Zhang; Yuhua Zhan (World Journal of Microbiology and Biotechnology, 2022)
Nitrogen metabolism is the most basic process of material and energy metabolism in living organisms, and processes involving the uptake and use of different nitrogen sources are usually tightly regulated at the transcriptional and post-transcriptional levels. Bacterial regulatory noncoding RNAs are novel post-transcriptional regulators that repress or activate the expression of target genes through complementarily pairing with target mRNAs; therefore, these noncoding RNAs play an important regulatory role in many physiological processes, such as bacterial substance metabolism and stress response. In recent years, a study found that noncoding RNAs play a vital role in the post-transcriptional regulation of nitrogen metabolism, which is currently a hot topic in the study of bacterial nitrogen metabolism regulation. In this review, we present an overview of recent advances that increase our understanding on the regulatory roles of bacterial noncoding RNAs and describe in detail how noncoding RNAs regulate biological nitrogen fixation and nitrogen metabolic engineering. Furthermore, our goal is to lay a theoretical foundation for better understanding the molecular mechanisms in bacteria that are involved in environmental adaptations and metabolically-engineered genetic modifications.

Immobilization of lead, copper, cadmium, nickel, and zinc in sediment by red mud: adsorption characteristics, mechanism, and effect of dosage on immobilization efficiency - Xianshang Bai; Jianwei Lin; Zhibin Zhang; Yanhui Zhan (Environmental Science and Pollution Research, 2022)

Prognostic implication and immunotherapy response prediction of a costimulatory molecule signature in kidney renal clear cell carcinoma - Gaoteng Lin; Yuanyuan Yang; Qingfu Feng; Fangfang Zhan; Chuangxin Sun; Yuanjie Niu; Gang Li (Immunogenetics, 2022)

Elastic-energy imaging condition based on energy-flow vector - Xiao-Yu Zhang; Yi Zheng; Chuan-Lin He; Zhan-Yuan Liang (Applied Geophysics, 2022)

Insight into the dynamic microbial community and core bacteria in composting from different sources by advanced bioinformatics methods - Yabin Zhan; Yuan Chang; Yueyue Tao; Hao Zhang; Yongfeng Lin; Jie Deng; Tiantian Ma; Guochun Ding; Yuquan Wei; Ji Li (Environmental Science and Pollution Research, 2022)

Reasonable application range of flocculation–solidification combined method in treatment of hydraulically dredged mud slurry - Rong-Jun Zhang; Zhi-Hao Xu; Jun-Jie Zheng; Lin-Wei Tu; Zhan-fang Huang (Marine Georesources & Geotechnology, 2022)

Contrasting effect of zirconium-, iron-, and zirconium/iron-modified attapulgites capping and amendment on phosphorus mobilization in sediment - Niuniu Liu; Wanyan Chen; Jianwei Lin; Yanhui Zhan (Environmental Science and Pollution Research, 2022)

Dispersivity variations of solute transport in heterogeneous sediments: numerical and experimental study - Ziqi Ma; Zhenxue Dai; Xiaoying Zhang; Chuanjun Zhan; Huili Gong; Lin Zhu; Corey D. Wallace; Mohamad Reza Soltanian (Stochastic Environmental Research and Risk Assessment, 2022)

Video target detection of East Asian migratory locust based on the MOG2-YOLOv4 network - Zhao Bai; Zhan Tang; Lei Diao; Shuhan Lu; Xuchao Guo; Han Zhou; Chengqi Liu; Lin li (International Journal of Tropical Insect Science, 2022)

Induction and Genomic Analysis of a Lysogenic Phage of Hafnia paralvei - Lingting Pan; Dengfeng Li; Yigang Tong; Wei Lin; Weinan Qin; Lihua Xu; Pingping Zhan (Current Microbiology, 2022)

The Key Regulator of Necroptosis, RIP1 Kinase, Contributes to the Formation of Astrogliosis and Glial Scar in Ischemic Stroke - Yong-Ming Zhu; Liang Lin; Chao Wei; Yi Guo; Yuan Qin; Zhong-Sheng Li; Thomas A. Kent; Claire E. McCoy; Zhan-Xiang Wang; Yong Ni; Xian-Yong Zhou; Hui-Ling Zhang (Translational Stroke Research, 2021)
Necroptosis initiation relies on the receptor-interacting protein 1 kinase (RIP1K). We recently reported that genetic and pharmacological inhibition of RIP1K produces protection against ischemic stroke-induced astrocytic injury. However, the role of RIP1K in ischemic stroke-induced formation of astrogliosis and glial scar remains unknown. Here, in a transient middle cerebral artery occlusion (tMCAO) rat model and an oxygen and glucose deprivation and reoxygenation (OGD/Re)-induced astrocytic injury model, we show that RIP1K was significantly elevated in the reactive astrocytes. Knockdown of RIP1K or delayed administration of RIP1K inhibitor Nec-1 down-regulated the glial scar markers, improved ischemic stroke-induced necrotic morphology and neurologic deficits, and reduced the volume of brain atrophy. Moreover, knockdown of RIP1K attenuated astrocytic cell death and proliferation and promoted neuronal axonal generation in a neuron and astrocyte co-culture system. Both vascular endothelial growth factor D (VEGF-D) and its receptor VEGFR-3 were elevated in the reactive astrocytes; simultaneously, VEGF-D was increased in the medium of astrocytes exposed to OGD/Re. Knockdown of RIP1K down-regulated VEGF-D gene and protein levels in the reactive astrocytes. Treatment with 400 ng/ml recombinant VEGF-D induced the formation of glial scar; conversely, the inhibitor of VEGFR-3 suppressed OGD/Re-induced glial scar formation. RIP3K and MLKL may be involved in glial scar formation. Taken together, these results suggest that RIP1K participates in the formation of astrogliosis and glial scar via impairment of normal astrocyte responses and enhancing the astrocytic VEGF-D/VEGFR-3 signaling pathways. Inhibition of RIP1K promotes the brain functional recovery partially via suppressing the formation of astrogliosis and glial scar. Graphical Abstract

GW10, a member of P450 subfamily regulates grain size and grain number in rice - Penglin Zhan; Xin Wei; Zhili Xiao; Xiaoling Wang; Shuaipeng Ma; Shaojun Lin; Fangping Li; Suhong Bu; Zupei Liu; Haitao Zhu; Guifu Liu; Guiquan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Negative‐pressure irrigation improves water and fertilizer use efficiencies and fruit yield of greenhouse tomato on the North China Plain* - Yinkun Li; Xuzhang Xue; Fan Xu; Wenzhong Guo; Minjie Duan; Sen Lin; Youli Li; Zhan Wang (Irrigation and Drainage, 2021)
Water and fertilizer supply are the main factors limiting greenhouse vegetable production on the North China Plain. This study tested the hypothesis that negative‐pressure irrigation is advantageous for reducing water and fertilizer application compared with drip irrigation in a greenhouse. Three treatments (drip irrigation + optimal fertilizer [DOF], drip irrigation + Yamazaki tomato nutrient solution [DNS], and negative‐pressure irrigation + Yamazaki tomato nutrient solution [NNS]) were applied in a greenhouse tomato double‐cropping system conducted in consecutive spring–summer and autumn–winter seasons. Soil moisture content, nitrate‐nitrogen (N) concentration, fruit yield, total N uptake ( N u ), irrigation water productivity, and partial factor productivity of applied fertilizer were analysed. The seasonal variation of soil moisture and nitrate‐N contents in the 0–20‐cm soil layer for NNS treatment was stable. Nitrate‐N accumulated after the final harvest in the autumn–winter season of NNS treatment was significantly less than under DOF and DNS. Despite lower water and nutrient inputs, NNS showed higher N u and fruit yield than DOF and DNS. These results demonstrated that negative‐pressure irrigation can reduce irrigation water and nutrient inputs and nitrate‐N accumulation in the soil, and significantly improve water and fertilizer use efficiency in greenhouse‐grown tomato compared with those under drip irrigation.

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Effects of the seasonal variation in chlorophyll concentration on sea surface temperature in the global ocean - Jinfeng Ma; Hailong Liu; Pengfei Lin; Haigang Zhan (Acta Oceanologica Sinica, 2021)

Sediment Coarsening in Tidal Flats and Stable Coastline of the Abandoned Southern Yellow River Sub-Delta in Response to Fluvial Sediment Flux Decrease During the Past Decades - Lin Zeng; Chao Zhan; Qing Wang; Xianbin Liu; Longsheng Wang; Xueyan Li; Xin Wang; Xiang Yu; Jinzhi Zhang; Buli Cui (Frontiers in Marine Science, 2021)
Due to remarkable reduction of sediment supply, the vulnerability of Yellow River deltaic system increased and ecological impacts occurred to some extent. To have a comprehensive and quantitative understanding of the morphological evolution of deltas, surficial sediments of tidal flat along the abandoned southern Yellow River sub-delta and two adjacent coastal units were systematically collected and evaluated by grain-size analysis in the study. The results reveal that surficial sediments of the abandoned southern Yellow River sub-delta have been coarsening significantly since the 1980s, as characterized by a decrease in both the mud content and the clay/mud ratio. In particular, the transition from cohesive to non-cohesive sediment was completed between 2007 and 2013. With a sharp decrease in sediment flux from the Yellow River estuary, the flood currents from the submarine coastal slope carry few fine particles into the tidal zone, whereas the ebb currents with reverse direction remove some fine particles from the tidal flat. This is a major cause of sediment coarsening in the tidal flat. As sediment coarsening, the coastline of the abandoned southern Yellow River sub-delta has remained stable. The significant change in the grain size of the tidal flat surficial sediments may have a profound impact on the future coastal geomorphic evolution.

Master regulator NtrC controls the utilization of alternative nitrogen sources in Pseudomonas stutzeri A1501 - Zhimin Yang; Qin Li; Yongliang Yan; Xiubin Ke; Yueyue Han; Shaoyu Wu; Fanyang Lv; Yahui Shao; Shanshan Jiang; Min Lin; Yunhua Zhang; Yuhua Zhan (World Journal of Microbiology and Biotechnology, 2021)
Pseudomonas stutzeri A1501 is a model strain used to study associative nitrogen fixation, and it possesses the nitrogen regulatory NtrC protein in the core genome. Nitrogen sources represent one of the important factors affecting the efficiency of biological nitrogen fixation in the natural environment. However, the regulation of NtrC during nitrogen metabolism in P. stutzeri A1501 has not been clarified. In this work, a phenotypic analysis of the ntrC mutant characterized the roles of NtrC in nitrogen metabolism and the oxidative stress response of P. stutzeri A1501. To systematically identify NtrC-controlled gene expression, RNA-seq was performed to further analyse the gene expression differences between the wild-type strain and the ∆ ntrC mutant under nitrogen fixation conditions. A total of 1431 genes were found to be significantly altered by ntrC deletion, among which 147 associative genes had NtrC-binding sites, and the pathways for nitrogen fixation regulation, nitrogenous compound acquisition and catabolism and nitrate assimilation were discussed. Furthermore, the oxidative stress-related gene ( katB ), which was upregulated by ntrC deletion, was suggested to be a potential target gene of NtrC, thus highlighting the importance of NtrC in nitrogenase protection against oxygen damage. Based on these findings, we propose that NtrC is a high-ranking element in the regulatory network of P. stutzeri A1501 that controls a variety of nitrogen metabolic and oxidative stress responsive traits required for adaptation to complex rhizosphere environments.

Diagnostic value of galactomannan test in non-immunocompromised critically ill patients with influenza-associated aspergillosis: data from three consecutive influenza seasons - Linna Huang; Yingfang Zhang; Lin Hua; Qingyuan Zhan (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Interaction between β-lactam antibiotic and phosphorus-accumulating organisms - Rong Huang; Jing Lan; Chaoguo Zhan; Yanhui Ge; Lin Zhao (Environmental Science and Pollution Research, 2021)

Disrupted white matter functional connectivity in aMCI APOEε4 carriers: a resting-state study - Hua Lin; Muwei Li; Yang Zhan; Li Lin; Kun Yang; Shimin Hu; Ying Han (Brain Imaging and Behavior, 2021)

Human papillomavirus prevalence among men who have sex with men in China: a systematic review and meta-analysis - Yiguo Zhou; Yi-Fan Lin; Lei Gao; Jianghong Dai; Ganfeng Luo; Lanying Li; Tanwei Yuan; Peiyang Li; Yuewei Zhan; Yanxiao Gao; Huachun Zou (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Potential benefits of liming to acid soils on climate change mitigation and food security - Yan Wang; Zhisheng Yao; Yang Zhan; Xunhua Zheng; Minghua Zhou; Guangxuan Yan; Lin Wang; Christian Werner; Klaus Butterbach‐Bahl (Global Change Biology, 2021)
Globally, about 50% of all arable soils are classified as acidic. As crop and plant growth are significantly hampered under acidic soil conditions, many farmers, but increasingly as well forest managers, apply lime to raise the soil pH. Besides its direct effect on soil pH, liming also affects soil C and nutrient cycles and associated greenhouse gas (GHG) fluxes. In this meta‐analysis, we reviewed 1570 observations reported in 121 field‐based studies worldwide, to assess liming effects on soil GHG fluxes and plant productivity. We found that liming significantly increases crop yield by 36.3%. Also, soil organic C (SOC) stocks were found to increase by 4.51% annually, though soil respiration is stimulated too (7.57%). Moreover, liming was found to reduce soil N 2 O emission by 21.3%, yield‐scaled N 2 O emission by 21.5%, and CH 4 emission and yield‐scaled CH 4 emission from rice paddies by 19.0% and 12.4%, respectively. Assuming that all acid agricultural soils are limed periodically, liming results in a total GHG balance benefit of 633−749 Tg CO 2 ‐eq year −1 due to reductions in soil N 2 O emissions (0.60−0.67 Tg N 2 O‐N year −1 ) and paddy soil CH 4 emissions (1.75−2.21 Tg CH 4 year −1 ) and increases in SOC stocks (65.7–110 Tg C year −1 ). However, this comes at the cost of an additional CO 2 release (c. 624–656 Tg CO 2 year −1 ) deriving from lime mining, transport and application, and lime dissolution, so that the overall GHG balance is likely neutral. Nevertheless, liming of acid agricultural soils will increase yields by at least 6.64 × 10 8 Mg year −1 , covering the food supply of 876 million people. Overall, our study shows for the first time that a general strategy of liming of acid agricultural soils is likely to result in an increasing sustainability of global agricultural production, indicating the potential benefit of liming acid soils for climate change mitigation and food security.

What’s the best way to achieve successful mainstream partial nitritation-anammox application? - Songkai Qiu; Zebing Li; Yuansheng Hu; Lin Shi; Rui Liu; Lei Shi; Lujun Chen; Xinmin Zhan (Critical Reviews in Environmental Science and Technology, 2021)

Status of the saker falcon in China - Jinbiao Sun; Andrew Dixon; Zhongru Gu; Zhenzhen Lin; Xiangjiang Zhan (Science China Life Sciences, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

PCDD/Fs characteristics in flue gas and surrounding environment of iron and steel smelting industry - Mingxiu Zhan; Yufeng Ma; Tong Chen; Xiaoqing Lin; Shiying Zhang; Shuaixi Xu; Xiaodong Li; Jianhua Yan (Environmental Science and Pollution Research, 2021)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Remediation of contaminated soil and groundwater using chemical reduction and solidification/stabilization method: a case study - Shi-Feng Lu; Yu-Lin Wu; Zhan Chen; Tao Li; Chao Shen; Lin-Kang Xuan; Ling Xu (Environmental Science and Pollution Research, 2021)

Engrafted primary type-2 astrocytes improve the recovery of the nigrostriatal pathway in a rat model of Parkinson's disease - Yanyun Sun; Xiao-jun Lu; Xinghui Fu; Ye Zhang; Yan Zhan; Jiabing Liu; Lingxia Zhao; Chun-lin Xia (Molecular and Cellular Biochemistry, 2021)

The novel three-dimensional pulse images analyzed by dynamic L-cube polynomial model - Ching-Hsing Luo; Zhan Zhang; Bo Peng; Xiaohua Xie; Tsung-Lin Lee; Liang-Miin Tsai (Medical & Biological Engineering & Computing, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Genotyping-by-sequencing to determine the genetic structure of a Tibetan medicinal plant Swertia mussotii Franch. - Yan Qiao; Fengxian Guo; Naxin Huo; Lin Zhan; Jiaqing Sun; Xixi Zuo; Zeguang Guo; Yong Q. Gu; Yi Wang; Yue Liu (Genetic Resources and Crop Evolution, 2021)

Injection route affects intra-articular hyaluronic acid distribution and clinical outcome in viscosupplementation treatment for knee osteoarthritis: a combined cadaver study and randomized clinical trial - Jun Xiao; Yong Hu; Lin Huang; Zhi-Fa Huang; Wei-Zhou Jiang; Yu-Qiang Luo; Meng-Yan Jia; Di Chen; Zhan-Jun Shi (Drug Delivery and Translational Research, 2021)

Verification of the biomass transfer hypothesis under moderate grazing across the Tibetan plateau: a meta-analysis - Jian Sun; Tianyu Zhan; Miao Liu; Zhenchao Zhang; Yi Wang; Shiliang Liu; Gao-lin Wu; Guohua Liu; Atsushi Tsunekawa (Plant and Soil, 2021)

Interception of sedimentary phosphorus release by iron-modified calcite capping - Xiaoyun Bai; Jianwei Lin; Zhibin Zhang; Boyang Liu; Yanhui Zhan; Dazhu Hu (Journal of Soils and Sediments, 2021)

Suppression of phosphorus release from sediment using lanthanum carbonate as amendment - Yanhui Zhan; Mingyue Chang; Jianwei Lin (Environmental Science and Pollution Research, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Deep-Learning-Based Segmentation and Localization of White Matter Hyperintensities on Magnetic Resonance Images - Wenhao Jiang; Fengyu Lin; Jian Zhang; Taowei Zhan; Peng Cao; Silun Wang (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Ferrous iron-induced increases in capitate glandular trichome density and upregulation of CbHO-1 contributes to increases in blinin content in Conyza blinii - Tianrun Zheng; Maojia Wang; Junyi Zhan; Wenjun Sun; Qin Yang; Zhiyi Lin; Tongliang Bu; Zizhong Tang; Chenglei Li; Jun Yan; Zhi Shan; Hui Chen (Planta, 2020)

Underway Measurement of Dissolved Inorganic Carbon (DIC) in Estuarine Waters - Jinpei Yan; Qi Lin; Seng Chee Poh; Yuhong Li; Liyang Zhan (Journal of Marine Science and Engineering, 2020)
Dissolved inorganic carbon (DIC) is an important parameter of the marine carbonate system. Underway analyses of DIC are required to describe spatial and temporal changes of DIC in marine systems. In this study, we developed a microvolume flow detection method for the underway determination of DIC in marine waters, using gas-diffusion flow analysis in conjunction with electrical conductivity (EC) measurement. Only an acid carrier reagent (0.2 mol.L−1) and an ultrapure water acceptor are required for the DIC monitoring system. In this system, a sampling loop (100 µL) is used to quantify the injection sample volume, allowing micro-sample volume detection. The water sample reacts with the acid reagent to convert carbonate and bicarbonate species into CO2. The water sample is then carried into a gas-diffusion assembly, where the CO2 diffuses from the sampling stream into the acceptor stream. CO2 in the acceptor is detected subsequently by an electrical conductivity. The limit of DIC detection using ultrapure water is 0.16 mM. A good repeatability is obtained, with a relative standard deviation (RSD) of 0.56% (1 mM, n = 21). The time interval for detecting one sample is 5 min. During the observation period, measurements can be switched between standard solutions and water samples automatically. Accuracy and precision of the instrument is sufficient for the underway observation of marine DIC in estuarine waters.

Boron availability in top- and sub-soils as affected by topography and climate - Xin Zhang; Meng-Jia Li; Lin-Qing Zhan; Wei Wu; Hong-Bin Liu (Nutrient Cycling in Agroecosystems, 2020)

Characterization of bimetallic Fe/Ni nanoparticles supported by amphiphilic block copolymer and its application in removal of 1,1,1-trichloroethane in water - Kai Huang; Hao Bian; Meng Zhang; Cong Zhan; Can Li; Wei Zhang; Changzheng Cui; Qiang Lu; Kuangfei Lin; Jianhua Zhao (Environmental Science and Pollution Research, 2020)

Establishment and identification of primary bovine omasal epithelial cells - Zixuan Hu; Kang Zhan; Tianyu Yang; Guoqi Zhao; Miao Lin (In Vitro Cellular & Developmental Biology - Animal, 2020)

Whole brain radiotherapy induces cognitive dysfunction in mice: key role of gut microbiota - Xiao-Xiao Luo; Chun Yang; Gao-Feng Zhan; Shan Li; Dong-Yu Hua; Ai-Lin Luo; Xiang-Lin Yuan (Psychopharmacology, 2020)

Correction to: Combined use of calcium nitrate, zeolite, and anion exchange resin for controlling phosphorus and nitrogen release from sediment and for overcoming disadvantage of calcium nitrate addition technology - Yanhui Zhan; Xiaolong Wu; Jianwei Lin (Environmental Science and Pollution Research, 2020)

Combined use of calcium nitrate, zeolite, and anion exchange resin for controlling phosphorus and nitrogen release from sediment and for overcoming disadvantage of calcium nitrate addition technology - Yanhui Zhan; Xiaolong Wu; Jianwei Lin (Environmental Science and Pollution Research, 2020)

Streptomyces taklimakanensis sp. nov., an actinomycete isolated from the Taklimakan desert - Lin-Lin Yuan; Li-Li Zhang; Xiao-Xia Luo; Zhan-Feng Xia; Bei-Bei Sun; Hong Zeng (Antonie van Leeuwenhoek, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Influence of coexisting calcium and magnesium ions on phosphate adsorption onto hydrous iron oxide - Jianwei Lin; Yuying Zhao; Yanhui Zhan; Yan Wang (Environmental Science and Pollution Research, 2020)

Assessment of iron-modified calcite/zeolite mixture as a capping material to control sedimentary phosphorus and nitrogen liberation - Yanhui Zhan; Yang Yu; Jianwei Lin; Xiaolong Wu; Yan Wang; Yuying Zhao (Environmental Science and Pollution Research, 2020)

Land use scenario simulation of mountainous districts based on Dinamica EGO model - Lin-lin Cheng; Mei Liu; Jia-qi Zhan (Journal of Mountain Science, 2020)

Revision surgery after instrumental fixation in patient with butterfly vertebra: a case report - Jiheng Zhan; Yufeng Wang; Bolai Chen; Dingkun Lin (Acta Neurologica Belgica, 2020)

Validation of micrografting to analyze compatibility, shoot growth, and root formation in micrografts of kiwifruit (Actinidia spp.) - Wen-Wu Bao; Xiao-Chen Zhang; A-Lin Zhang; Lei Zhao; Qiao-Chun Wang; Zhan-De Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

A critical review on environmental implications, recycling strategies, and ecological remediation for mine tailings - Da-Mao Xu; Chang-Lin Zhan; Hong-Xia Liu; Han-Zhi Lin (Environmental Science and Pollution Research, 2019)

Atmospheric deposition and air–soil exchange of polybrominated diphenyl ethers (PBDEs) in a background site in Central China - Lingxi Zhan; Tian Lin; Hairong Cheng; Zuwu Wang; Zhineng Cheng; Deng Zhou; Zhengxin Qin; Gan Zhang (Environmental Science and Pollution Research, 2019)

Aflatoxin B1 enhances pyroptosis of hepatocytes and activation of Kupffer cells to promote liver inflammatory injury via dephosphorylation of cyclooxygenase-2: an in vitro, ex vivo and in vivo study - Li-Yin Zhang; Deng-Lin Zhan; Yuan-Yuan Chen; Wei-Hua Wang; Cheng-Yong He; Yi Lin; Yu-Chun Lin; Zhong-Ning Lin (Archives of Toxicology, 2019)

An integrated strategy to identify genes responsible for sesquiterpene biosynthesis in turmeric - Jingru Sun; Guanghong Cui; Xiaohui Ma; Zhilai Zhan; Ying Ma; Zhongqiu Teng; Wei Gao; Yanan Wang; Tong Chen; Changjiangsheng Lai; Yujun Zhao; Jinfu Tang; et al. (Plant Molecular Biology, 2019)

Isolation of a New PAK1 Gene from Sea Cucumber (Apostichopus japonicus) and Its Expression Analysis and Function Characterization - Liyuan Ren; Kaiquan Li; Yaoyao Zhan; Yi Wang; Yao Yu; Yang Chen; Kai Lin; Jian Song; Yaqing Chang (Journal of Ocean University of China, 2019)

Visualizing DC morphology and T cell motility to characterize DC-T cell encounters in mouse lymph nodes under mTOR inhibition - Qiaoya Lin; Zheng Liu; Meijie Luo; Hao Zheng; Sha Qiao; Chenlu Han; Deqiang Deng; Zhan Fan; Yafang Lu; Zhihong Zhang; Qingming Luo (Science China Life Sciences, 2019)

Analysis of the elemental spectral characteristics of single elemental capture spectrum log using Monte-Carlo simulation - Chang-Lin Lan; Xu-Wen Zhan; Hong-Liang Wu; Yi Zhang; Tong Liu; Zhou Feng; Tao Lv (Applied Geophysics, 2019)

Study on the relationship between waste classification, combustion condition and dioxin emission from waste incineration - Xiaodong Li; Yunfeng Ma; Mengmei Zhang; Mingxiu Zhan; Peiyue Wang; Xiaoqing Lin; Tong Chen; Shengyong Lu; Jianhua Yan (Waste Disposal & Sustainable Energy, 2019)

The analysis of clinical and laboratory data: a large outbreak of dengue fever in Chaozhou, Guangdong province, China - Fen Lin; Hui Yang; Lin Zhang; Sen-Hai Fang; Xiao-Fen Zhan; Li-Ye Yang (Archives of Virology, 2019)

Relationships between body weight and other morphological traits in young sea cucumbers Apostichopus japonicas - Yaoyao Zhan; Weijie Zhang; Chen Ge; Kai Lin; Guang Li; Jian Song; Yaqing Chang (Journal of Oceanology and Limnology, 2019)

Assessment of sediment capping with zirconium-modified bentonite to intercept phosphorus release from sediments - Jianwei Lin; Siqi He; Yanhui Zhan; Zhe Zhang; Xiaolong Wu; Yang Yu; Yuying Zhao; Yan Wang (Environmental Science and Pollution Research, 2019)

Insights into removal of tetracycline by persulfate activation with peanut shell biochar coupled with amorphous Cu-doped FeOOH composite in aqueous solution - Jian Xu; Xueliang Zhang; Cheng Sun; Jinzhong Wan; Huan He; Fei Wang; Yuxuan Dai; Shaogui Yang; Yusuo Lin; Xinhua Zhan (Environmental Science and Pollution Research, 2019)

Complete Genome Sequence of Bacillus cereus CC-1, A Novel Marine Selenate/Selenite Reducing Bacterium Producing Metallic Selenides Nanomaterials - Lin Che; Weiping Xu; Jingjing Zhan; Lei Zhang; Lifen Liu; Hao Zhou (Current Microbiology, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Population genetic patterns of the solitary tunicate, Molgula manhattensis, in invaded Chinese coasts: large-scale homogeneity but fine-scale heterogeneity - Yiyong Chen; Shiguo Li; Yaping Lin; Hongjun Li; Aibin Zhan (Marine Biodiversity, 2018)

Characterization of the complete chloroplast genome sequence of Cardamine macrophylla (Brassicaceae) - Ting Ren; Yanci Yang; Jiao Wang; Ruiting Zhang; Zhan-Lin Liu (Conservation Genetics Resources, 2018)

Physiological and anatomical response of foliar silicon application to Dendrocalamus brandisii plantlet leaves under chilling - Hui Zhan; Li-ya Zhang; Lin Deng; Zhao-hui Niu; Mao-biao Li; Chang-ming Wang; Shuguang Wang (Acta Physiologiae Plantarum, 2018)

A Novel MYCN Variant Associated with Intellectual Disability Regulates Neuronal Development - Xiuya Yu; Liyuan Hu; Xu Liu; Guodong Zhan; Mei Mei; Huijun Wang; Xiaohua Zhang; Zilong Qiu; Wenhao Zhou; Lin Yang (Neuroscience Bulletin, 2018)

Industrial air pollution and low birth weight: a case-control study in Texas, USA - Xi Gong; Yan Lin; F. Benjamin Zhan (Environmental Science and Pollution Research, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Four first records of trichodinid (Ciliophora: Peritrichia) ectoparasites from cultured molluscs and fishes in China - Zifeng Zhan; Hong Zeng; Nengfeng Lin; Kuidong Xu (Acta Oceanologica Sinica, 2018)

Short-term effects of ambient air pollutants and myocardial infarction in Changzhou, China - Yongquan Yu; Shen Yao; Huibin Dong; Minghui Ji; Zhiyong Chen; Guiying Li; Xingjuan Yao; Shou-Lin Wang; Zhan Zhang (Environmental Science and Pollution Research, 2018)

Whole-genome sequence and genome annotation of Xanthomonas citri pv. mangiferaeindicae, causal agent of bacterial black spot on Mangifera indica - Feng Liu; Xiong-chang Ou; Ru-lin Zhan (Archives of Microbiology, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Nutrient Recovery from Digestate of Anaerobic Digestion of Livestock Manure: a Review - Lin Shi; Walquiria Silva Simplicio; Guangxue Wu; Zhenhu Hu; Hongying Hu; Xinmin Zhan (Current Pollution Reports, 2018)

CXCL5 regulation of proliferation and migration in human non-small cell lung cancer cells - Lin Wang; Lin Shi; Jie Gu; Cheng Zhan; Junjie Xi; Jianyong Ding; Di Ge (Journal of Physiology and Biochemistry, 2018)

Variations in the northern permafrost boundary over the last four decades in the Xidatan region, Qinghai–Tibet Plateau - Jing Luo; Fu-jun Niu; Zhan-ju Lin; Ming-hao Liu; Guo-an Yin (Journal of Mountain Science, 2018)

Multi-type sensor placement and response reconstruction for building structures: Experimental investigations - Rong-Pan Hu; You-Lin Xu; Sheng Zhan (Earthquake Engineering and Engineering Vibration, 2018)

Complete chloroplast genome sequence of Pedicularis cheilanthifolia, an alpine plant in China - Ruiting Zhang; Jiao Wang; Kai Han; Ting Ren; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of the Cortusa matthioli subsp. pekinensis (Primulaceae) - Jiao Wang; Ruiting Zhang; Ting Ren; Kai Han; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Practical method and application study for predicting cyclic accumulative deformations of the saturated soft clay - Lin-lin He; Yuan-zhan Wang; Shu-zhao Li; Zhao-yang Wang (Journal of Mountain Science, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Investigation of relationships between meteorological conditions and high PM10 pollution in a megacity in the western Yangtze River Delta, China - Yaqun Zu; Lin Huang; Jianlin Hu; Zhan Zhao; Hang Liu; Hongliang Zhang; Qi Ying; Mindong Chen (Air Quality, Atmosphere & Health, 2017)

Bioactivity, toxicity and detoxification assessment of Dioscorea bulbifera L.: a comprehensive review - Xiao-Rui Guan; Lin Zhu; Zhan-Gang Xiao; Yi-Lin Zhang; Hu-Biao Chen; Tao Yi (Phytochemistry Reviews, 2017)

Establishment of immortalized mouse intestinal epithelial cells line and study of effects of Arg-Arg on inflammatory response - Kang Zhan; Maocheng Jiang; Yannan Sui; Kang Yan; Miao Lin; Guoqi Zhao (In Vitro Cellular & Developmental Biology - Animal, 2017)

Characterization of the complete chloroplast genome sequence of Lysionotus pauciflorus (Gesneriaceae) - Ting Ren; Wei Zheng; Kai Han; Shuyun Zeng; Jianhua Zhao; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Effect of humic acid preloading on phosphate adsorption onto zirconium-modified zeolite - Jianwei Lin; Zhe Zhang; Yanhui Zhan (Environmental Science and Pollution Research, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Complete chloroplast genome sequence of Chinese larch (Larix potaninii var. chinensis), an endangered conifer endemic to China - Kai Han; Jianfang Li; Shuyun Zeng; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of Platycarya strobilacea (Juglandaceae) - Jing Yan; Kai Han; Shuyun Zeng; Peng Zhao; Keith Woeste; Jianfang Li; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Different response of an elite Bt restorer line of hybrid rice (Oryza sativa L.) in adaptation to nitrogen deficiency - Yang Jiang; Lin Ling; Lingli Zhang; Abigail Domingo; Mingli Cai; Chengfang Li; Ming Zhan; Jinping Wang; Cougui Cao (Acta Physiologiae Plantarum, 2017)

Emission and distribution of PCDD/Fs, chlorobenzenes, chlorophenols, and PAHs from stack gas of a fluidized bed and a stoker waste incinerator in China - Tianjiao Wang; Tong Chen; Xiaoqing Lin; Mingxiu Zhan; Xiaodong Li (Environmental Science and Pollution Research, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Establishment of primary bovine intestinal epithelial cell culture and clone method - Kang Zhan; Miao Lin; Ming-Mei Liu; Yang-Nan Sui; Guo-Qi Zhao (In Vitro Cellular & Developmental Biology - Animal, 2017)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Zhen’an Yang; Wan Xiong; Yingyi Xu; Lin Jiang; Erxiong Zhu; Wei Zhan; Yixin He; Dan Zhu; Qiuan Zhu; Changhui Peng; Huai Chen (Environmental Monitoring and Assessment, 2016)

Complete chloroplast genome sequences of Rehmannia chingii, an endemic and endangered herb - Shuyun Zeng; Jianhua Zhao; Kai Han; Zhan-Lin Liu (Conservation Genetics Resources, 2016)

Biological characterization of bovine mammary epithelial cell lines immortalized by HPV16 E6/E7 and SV40T - Kang Zhan; Miao Lin; Qian-Ming Zhao; Jin-Shun Zhan; Guo-Qi Zhao (In Vitro Cellular & Developmental Biology - Animal, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Performance comparison of permafrost models in Wudaoliang Basin, Qinghai-Tibet Plateau, China - Guo-an Yin; Fu-jun Niu; Zhan-ju Lin; Jing Luo; Ming-hao Liu (Journal of Mountain Science, 2016)

The climatic impacts of land use and land cover change compared among countries - Jiyuan Liu; Quanqin Shao; Xiaodong Yan; Jiangwen Fan; Jinyan Zhan; Xiangzheng Deng; Wenhui Kuang; Lin Huang (Journal of Geographical Sciences, 2016)

Probabilistic Analysis of Earthquake-Led Water Contamination: A Case of Sichuan, China - Yan Yang; Lin Li; F. Benjamin Zhan; Yanhua Zhuang (Pure and Applied Geophysics, 2016)

Emission and distribution of PCDD/Fs and CBzs from two co-processing RDF cement plants in China - Tong Chen; Ming-Xiu Zhan; Xiao-qing Lin; Ye-qing Li; Jiang Zhang; Xiao-Dong Li; Jian-hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Fingerprint analysis and multi-component determination of Zibu Piyin recipe by HPLC with DAD and Q-TOF/MS method - Hong Xiang; Huiying Xu; Libin Zhan; Lin Zhang (Natural Product Research, 2016)

miR-138-1* regulates aflatoxin B1-induced malignant transformation of BEAS-2B cells by targeting PDK1 - Yun Wang; Zhan Zhang; Huanqiang Wang; Yudong Zhang; Minghui Ji; Hengsen Xu; Chao Wang; Zhenzhen Sun; Weimin Gao; Shou-Lin Wang (Archives of Toxicology, 2016)

Simultaneous determination of six constituents in Mahuang Fuzi Xixin by UPLC-PDA–MS/MS - Lin Zhang; Chengying Wang; Dezu Miao; Dan Yuan; Kaishun Bi; Jingyu Yang; Libin Zhan (Natural Product Research, 2015)

Assessing the authenticity of commercial deep-sea drinking water by chemical and isotopic approaches - Tsung-Ren Peng; Wen-Jui Liang; Tsang-Sen Liu; Yu-Wen Lin; Wen-Jun Zhan (Isotopes in Environmental and Health Studies, 2015)

Immobilization of phosphorus from water and sediment using zirconium-modified zeolites - Mengjuan Yang; Jianwei Lin; Yanhui Zhan; Zhiliang Zhu; Honghua Zhang (Environmental Science and Pollution Research, 2015)

Isolation and characterization of microsatellite loci in the dog-faced water snake Cerberus rynchops (Colubridae) - Xiao-Hui Lv; Shu-Zhan Zhao; Xiao-Xiao Zheng; Long-Hui Lin (Conservation Genetics Resources, 2015)

Development of twelve nuclear microsatellites in the endemic herb Rehmannia chingii using next generation sequencing - Yuan Ma; Chunyan Liu; Zhong-Hu Li; Jianfang Li; Zhan-Lin Liu (Conservation Genetics Resources, 2015)

Development and characterization of 16 polymorphic microsatellite markers for the highly invasive ascidian, Ciona savignyi - Ping Ni; Yaping Lin; Yiyong Chen; Haitao Li; Yan Zhao; Aibin Zhan (Conservation Genetics Resources, 2015)

Introduction and use of non‐native species for aquaculture in C hina: status, risks and management solutions - Yaping Lin; Zexia Gao; Aibin Zhan (Reviews in Aquaculture, 2015)
Aquaculture is one of the fast‐growing industries in the past decades. The fast expansion of aquaculture largely relies on the introduction and use of non‐native species. This forms a paradox: some species significantly contribute to the fast expansion of aquaculture, while negative effects associated with unregulated introduction and irresponsible use of non‐native species are increasing in number and area affected. However, lessons from reported disasters are slowly learned, and risks raised have been highly overlooked. Here, we discuss the known and potential risks derived from the introduction and use of non‐native species in China to urge the necessity of incorporating sound management into sustainable aquaculture. Sound management needs to be performed based on the characteristics of each aquaculture activity or related event. We discuss risks based on aquaculture activities or related events popularly employed in the past decades in China, including (i) transfers of non‐native species; (ii) fellow travellers, accidental introductions; (iii) artificial hybridization; and (iv) mass release of non‐native species for ranching. For each aquaculture activity or related event, we provide general background, status of this activity, risks raised and recommendations for management. Finally, we call for the collaboration of researchers from academia, government and aquaculture industry for proper risk assessment and sound management for sustainable development of aquaculture.

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

An equilibrium analysis of the land use structure in the Yunnan Province, China - Jiao Luo; Jinyan Zhan; Yingzhi Lin; Chunhong Zhao (Frontiers of Earth Science, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

An equilibrium analysis of the land use structure in the Yunnan Province, China - Jiao Luo; Jinyan Zhan; Yingzhi Lin; Chunhong Zhao (Frontiers of Earth Science, 2014)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

Using ADABOOST and Rough Set Theory for Predicting Debris Flow Disaster - Ping-Feng Pai; Lan-Lin Li; Wei-Zhan Hung; Kuo-Ping Lin (Water Resources Management, 2014)

Changes in land use and agricultural production structure before and after the implementation of grain for green program in Western China — taking two typical counties as examples - Ping Zhou; An-bang Wen; Dong-chun Yan; Zhong-lin Shi; Jin Guo; Zhan-sheng Ju; Yi-lan Zhang (Journal of Mountain Science, 2014)

Three new diterpenoids from the resin of Liquidambar formosana - Hong-Jie Shang; Dan-Yi Li; Wen-Jing Wang; Zhan-Lin Li; Hui-Ming Hua (Natural Product Research, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

Comprehensive screening for multi-class veterinary drug residues and other contaminants in muscle using column-switching UPLC-MS/MS - Jia Zhan; Di-ming Xu; Shi-jie Wang; Ji Sun; Yin-jun Xu; Mei-lin Ni; Ju-yi Yin; Jie Chen; Xue-jun Yu; Zhi-qiang Huang (Food Additives & Contaminants: Part A, 2013)

Estimating groundwater recharge beneath irrigated farmland using environmental tracers fluoride, chloride and sulfate - Dan Lin; Menggui Jin; Xing Liang; Hongbin Zhan (Hydrogeology Journal, 2013)

Early to mid‐ H olocene rapid sea‐level rise and coastal response on the southern Yangtze delta plain, China - ZHANGHUA WANG; QING ZHAN; HAIYAN LONG; YOSHIKI SAITO; XIAOQIN GAO; XUXU WU; LIN LI; YANAN ZHAO (Journal of Quaternary Science, 2013)
We used accelerator mass spectrometry (AMS) 14 C‐dated sediments of the Holocene basal supratidal flat to upper tidal flat facies in 11 cores on the southern Yangtze delta plain to reconstruct relative sea levels of 8.5–8.0 cal ka BP. Three cores were further AMS 14 C dated and used to examine the evolution of sedimentary geomorphological environments in response to the rapid sea‐level rise during the early to mid‐Holocene. Results demonstrate relative sea‐level rise of around 30 mm a −1 from 8.5 to 8.3 cal ka BP and around 10 mm a −1 from 8.3 to 8.0 cal ka BP. Retrogradation from supratidal to lower tidal flat environments occurred in response to the rapid sea‐level rise at 8.5–8.3 cal ka BP, and aggradation from middle to upper tidal flat occurred at 8.3–7.9 cal ka BP. Further retreat of the tidal flat at 7.9–7.2 cal ka BP implies a mean sea‐level rise rate exceeding 5 mm a −1 at this time. We suggest that the rapid relative sea‐level rise during 8.3–8.5 cal ka BP and subsequent slower rise caused drastic changes in the coastal zone and that these changes are key phenomena for understanding the coastal response to future sea‐level rise.

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

Cytochrome P450 2A13 is an efficient enzyme in metabolic activation of aflatoxin G1 in human bronchial epithelial cells - Zhan Zhang; Xuejiao Yang; Yun Wang; Xichen Wang; Huiyuan Lu; Xiaoming Zhang; Xue Xiao; Shushu Li; Xinru Wang; Shou-Lin Wang (Archives of Toxicology, 2013)

Mechanism of BDE209-induced impaired glucose homeostasis based on gene microarray analysis of adult rat liver - Zhan Zhang; Zhen-Zhen Sun; Xue Xiao; Shixin Zhou; Xi-Chen Wang; Jun Gu; Liang-Lin Qiu; Xu-Hui Zhang; Qiujin Xu; Binghui Zhen; Xinru Wang; Shou-Lin Wang (Archives of Toxicology, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

A new cyclonerol derivative from a marine-derived fungus Ascotricha sp. ZJ-M-5 - Lei-Rui Xie; Dan-Yi Li; Zhan-Lin Li; Hui-Ming Hua; Pei-Le Wang; Xin Wu (Natural Product Research, 2013)

Glucose-6-phosphate dehydrogenase (G6PD) gene mutations detection by improved high-resolution DNA melting assay - Meichen Pan; Min Lin; Lin Yang; Jiaoren Wu; Xiaofen Zhan; Ying Zhao; Yingfang Wen; Guirong Liu; Liye Yang; Yingmu Cai (Molecular Biology Reports, 2013)

Preparation and characterization of surfactant-modified hydroxyapatite/zeolite composite and its adsorption behavior toward humic acid and copper(II) - Yanhui Zhan; Jianwei Lin; Jia Li (Environmental Science and Pollution Research, 2013)

Two new triterpenoid saponins from the husks of Xanthoceras sorbifolia - Zhan-Lin Li; Dan-Yi Li; Xiao-Meng He; Hui-Ming Hua (Natural Product Research, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

New sphingolipid psychotramide A–D from the stem of Psychotria sp. - Cui-Xian Zhang; Xi-Xin He; Shan-Yue Guan; Ying Zhong; Chao-Zhan Lin; Tian-Qin Xiong; Chen-Chen Zhu (Natural Product Research, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Influence of UGT genetic polymorphism on the interindividual variability in mitiglinide pharmacokinetic in Chinese - Jing-feng Xu; Zhan-qing Wang; Chen-xia Yan; Qian Xu; Lin Xu; Gang-tao Zhao; Yong-ge Yang (Medicinal Chemistry Research, 2012)

Application of 3D GPR attribute technology in archaeological investigations - Wen-Ke Zhao; Gang Tian; Bang-Bing Wang; Zhan-Jie Shi; Jin-Xin Lin (Applied Geophysics, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Identification and analysis of the metabolic functions of a high-salt-tolerant halophilic aromatic yeast Candida etchellsii for soy sauce production - Jie Feng; Xiao-Bei Zhan; Dong Wang; Li-Min Zhang; Chi-Chung Lin (World Journal of Microbiology and Biotechnology, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

Mapping of QTLs associated with important agronomic traits using three populations derived from a super hybrid rice Xieyou9308 - Yongshu Liang; Xiaodeng Zhan; Zhiqiang Gao; Zechuan Lin; Zhanlie Yang; Yinxin Zhang; Xihong Shen; Liyong Cao; Shihua Cheng (Euphytica, 2012)

Penehyclidine hydrochloride attenuates LPS-induced iNOS production by inhibiting p38 MAPK activation in endothelial cells - Jia Zhan; Zong-ze Zhang; Chang Chen; Kai Chen; Yan-lin Wang (Molecular Biology Reports, 2012)

Generation and application of anti-ouabain IgY antibodies - Ming Juan Zhang; Jun Yang; Can Zhan Zhu; Zong Ming Duan; Xiao Lin Niu (Molecular and Cellular Biochemistry, 2011)

Genomic sequencing and analysis of Chilli ringspot virus, a novel potyvirus - Dian Gong; Jian-Hua Wang; Zhan-Song Lin; Shao-Yan Zhang; Yu-Liang Zhang; Nai-Tong Yu; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2011)

The Applications of Satellite Based Remote Sensing Techniques in the Hydrological Assessment of Mine Water Supply and Management Systems - Mei Lin Shelp; Guosheng Zhan; Bill Upton (Mine Water and the Environment, 2011)

A new alkaloid from the marine-derived fungus Hypocrea virens - Tao Liu; Zhan-Lin Li; Yu Wang; Li Tian; Yue-Hu Pei; Hui-Ming Hua (Natural Product Research, 2011)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)

A novel prenylated xanthone from the stems and leaves of Calophyllum inophyllum - Zhan-Lin Li; Dan Liu; Dan-Yi Li; Hui-Ming Hua (Natural Product Research, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Single amino acid residue changes in subsite −1 of levansucrase from Zymomonas mobilis 10232 strongly influence the enzyme activities and products - Shuying Li; Yongliang Yan; Zhengfu Zhou; Haiying Yu; Yuhua Zhan; Wei Zhang; Ming Chen; Wei Lu; Shuzhen Ping; Min Lin (Molecular Biology Reports, 2011)

Application of statistical design for the optimization of microbial community of synthetic domestic wastewater - Yuancai Chen; Che-Jen Lin; Gavin Jones; Shiyu Fu; Huaiyu Zhan (Biodegradation, 2011)

Improvement of the CuZn-superoxide dismutase enzyme activity and stability as a therapeutic agent by modification with polysialic acids - Jian Rong Wu; Yi Lin; Zhi Yong Zheng; Chi Chung Lin; Xiao Bei Zhan; Ying Qiang Shen (Biotechnology Letters, 2010)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Improvement of an E. coli bioreporter for monitoring trace amounts of phenol by deletion of the inducible σ54-dependent promoter - Zixin Peng; Yongliang Yan; Yuquan Xu; Masahiro Takeo; Haiying Yu; Zhonglin Zhao; Yuhua Zhan; Wei Zhang; Min Lin; Ming Chen (Biotechnology Letters, 2010)

Simulation on the dynamics of forest area changes in Northeast China - Xiangzheng Deng; Qun’ou Jiang; Jinyan Zhan; Shujin He; Yingzhi Lin (Journal of Geographical Sciences, 2010)

Factors and mechanism driving the land-use conversion in Jiangxi Province - Jinyan Zhan; Nana Shi; Shujin He; Yingzhi Lin (Journal of Geographical Sciences, 2010)

A complete mitochondrial genome of wheat (Triticum aestivum cv. Chinese Yumai), and fast evolving mitochondrial genes in higher plants - Peng Cui; Huitao Liu; Qiang Lin; Feng Ding; Guoyin Zhuo; Songnian Hu; Dongcheng Liu; Wenlong Yang; Kehui Zhan; Aimin Zhang; Jun Yu (Journal of Genetics, 2009)

Benzoate Catabolite Repression of the Phenol Degradation in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Shuzhen Ping; Wei Lu; Wei Zhang; Ming Chen; Min Lin (Current Microbiology, 2009)

Genes Involved in the Benzoate Catabolic Pathway in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Ming Chen; Wei Lu; Shuying Li; Zixin Peng; Wei Zhang; Shuzhen Ping; Jin Wang; Min Lin (Current Microbiology, 2008)

T-2 toxin-induced apoptosis involving Fas, p53, Bcl-xL, Bcl-2, Bax and caspase-3 signaling pathways in human chondrocytes - Jing-hong Chen; Jun-ling Cao; Yong-lie Chu; Zhi-lun Wang; Zhan-tian Yang; Hong-lin Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Desferoxamine preconditioning protects against cerebral ischemia in rats by inducing expressions of hypoxia inducible factor 1α and erythropoietin - Yun-Xia Li; Su-Ju Ding; Lin Xiao; Wei Guo; Qing Zhan (Neuroscience Bulletin, 2008)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Isolation and characterization of 18 genes encoding α- and β-expansins in wheat (Triticum aestivum L.) - Zhan Lin; Zhongfu Ni; Yi Zhang; Yingyin Yao; Haiyan Wu; Qixin Sun (Molecular Genetics and Genomics, 2005)

Reduced MTA1 Expression by RNAi Inhibits in Vitro Invasion and Migration of Esophageal Squamous Cell Carcinoma Cell Line - Haili Qian; Ning Lu; Liyan Xue; Xiao Liang; Xueyan Zhang; Ming Fu; Yongqiang Xie; Qimin Zhan; Zhihua Liu; Chen Lin (Clinical & Experimental Metastasis, 2005)

Solution-phase reductive cyclization of 2-quinoxalinol analogs: Systematic study of parallel synthesis - Xiang-Hong Wu; Gang Liu; Jing Zhang; Zhan-Guo Wang; Song Xu; Suo-De Zhang; Liang Zhang; Lin Wang (Molecular Diversity, 2004)